Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 617474056 species occurrences available in GBIF matching the query: { "and" : [ "BasisOfRecord is Human Observation", "Issue is Coordinate rounded" ] } The dataset includes 617474056 records from 3738 constituent datasets: 166 records from Zielbach (Töll). 96 records from BIRDRACE Emslandracer. 120 records from BIRDRACE The early birds. 911726 records from WildNet - Queensland Wildlife Data. 453 records from National Plant Monitoring Scheme - England, Scotland, Wales. 90 records from Wildlife Sightings in the City of Logan. 115 records from Antarctic Pycnogonids II. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 10 records from Oberservation of birds at station PS14/143 along 49° West. 1548 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 9064 records from Big Island Invasive Species Committee - Pest Reports - 2005-2010. 86 records from Fliegenhaupt Marksuhl. 43 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 41 records from Newhaven Sanctuary observations. 97 records from BIRDRACE NABUhu Trier!. 989 records from IBF Monitoring of Fungi. 130 records from Artenvielfalt auf dem Schulgelände. 1809 records from BenthosChukchiFN762_1976_Falk5. 454 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core GIK12392-1. 27 records from Caracterización floristica del Alto del Buey, Bahia Solano - Chocó. 161 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia.. 12 records from Antarctic Krill occurrence data from Spanish RV "Fruela". 69 records from BIRDRACE Pfeifenten. 135 records from Total foraminifera counts of multinet M12/3_MSN558. 236 records from Knechtweide (Kohlfurth). 18 records from Benthic macrofauna abundance of sediment core 12930-073. 827 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán. 89 records from Meniscus Midges (Dixidae) of Ireland. 232 records from Census of waterbird in Benin Flyway. 171 records from Alien Species in Poland - Animals. 780 records from Distribution of agglutinated foraminifers in sediment core Well 6406/8-1. 62 records from Registros de especies focales de fauna, Departamento del Quindío. 267 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 253 records from Mosquitoes (Culicidae) of Ireland. 274 records from BIRDRACE Asiola-Quartett. 1319 records from Amphibians and reptiles of Ireland. 45 records from Recursos hidrobiológicos de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia BIO. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 207791 records from Kenya Birdmap (Full protocol records). 28 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2. 5 records from Sächsische Schweiz (Pfaffenstein). 144 records from BIRDRACE Punkbirder Helgoland. 340 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 839 records from Biodiversidad íctica de la Isla Cayos de Albuquerque Reserva de Biosfera Seaflower-Proyecto Colombia BIO. 69 records from Naturpark Kottenforst-Ville 18.6.09. 1480 records from Helmintos parásitos de peces del sureste de México. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 61 records from Naturpark Kottenforst-Ville 15.6.09. 1016 records from ConDidact Citizen Science Surveys - Spiders 2011. 83 records from Roter Berg Werdau (Leubnitz). 38 records from Abundance of benthos infauna at station POS128/2_276. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 64 records from Mauernacker (Wettsaasen). 63 records from Total foraminifera counts of multinet M21/4_MSN706. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 173 records from FFH-Gebiet Klosterwasser/Burkau. 92 records from Wiesen in der Grünen Mitte. 152 records from Wildkräuter. 108 records from Total foraminifera counts of multinet M21/2_MSN629. 96 records from Plasm bearing foraminifera counts of multinet M21/2_MSN650. 122 records from Inventory of plant species in the municipal forests of Nonsinasson, Gbede, Pele, Toukou, Fita, Wogbo, Bobe (Benin, West Africa). 1229 records from Registros biológicos de predios promocionados como Reservas Naturales de la Sociedad Civil-RNSC en el Cañón de Amaime, municipio El Cerrito, Valle del Cauca, Colombia.. 114 records from BIRDRACE LiLaLau. 82 records from Total foraminifera counts of multinet M12/3_MSN560. 48 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 1002 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 270 records from Registros biológicos de aves Distrito de Manejo Integrado Musichi y Santuario de Fauna y Flora los Flamencos, La Guajira.. 755 records from Freiburger GEO-Tag der Artenvielfalt. 2620 records from Copepodos Chile. 59 records from Schulteich Freie Waldorfschule Darmstadt. 72 records from Ostfriesland. 629 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 130 records from ABC_Ndangopuma_hills_eventdata_25_11_2005. 44461 records from Weed and native flora data for the Swan Coastal Plain. 370 records from Estudio de la estructura genética espacial de la palma Elaeis oleifera. 99 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 1331 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 371 records from Freshwater fish records via iRecord. 18 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 527 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 3786 records from Vascular plants of Amrum 2007-2008. 159 records from Total foraminifera counts of multinet M36/6_MSN1196. 1 records from National Dormouse Database (NDD). 2808 records from Weddell Sea macrozoobenthos EASIZ I. 2170 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 500 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 103 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 4149 records from Temporal evolution of zooplankton by WP2 net in the Northwestern Mediterranean Sea, Villefranche-sur-mer 2004-2010.. 12 records from Art´n Vielfalt im Kinderwald. 4836 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 135 records from Waldi-Weiher. 171 records from Total foraminifera counts of multinet SO118_MSN1252. 16 records from Benthic macrofauna abundance of sediment core 13077-093. 459 records from Gewann Krampf (Heilbronn). 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 113 records from Abundance of radiolaria at station UT99-13-2. 210 records from Kongsfjorden/Spitsbergen - soft bottom fauna. 17 records from Benthic macrofauna abundance of sediment core 13201-002. 31 records from Circumpolar Seabird Monitoring Plan. 48 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8). 54 records from Fauna íctica del río Arquía, en las estribaciones del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 14883 records from DATAVES. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 364 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 372 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 69 records from Schulgarten mit Klasse 8a (Essen). 7 records from Planktic foraminifera abundance of Hole 53-418B. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 79 records from Birdrace-Bielefinken-Bielefeld. 107 records from Müritz-Nationalpark. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 4493 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 270 records from Wald am Schloss Wittgenstein Bad Laasphe. 28 records from Stadtpark Prinzengarten (Sigmaringen). 1437 records from Dinoflagellate cysts counts of sediment core MD95-2010. 35 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 180 records from Total foraminifera counts of multinet M21/1_MSN605. 66 records from Reptiles presentes en la ciénaga de Bete, municipio del Medio Atrato 2008. 281250 records from Quadrige. 85 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 18 records from Anfibios presentes en el Cerro Jánano. 41 records from Occurrence of Butterfly species recorded in Western and Brong Ahafo Regions of Ghana. 149 records from Abundance of radiolaria at station UT99-23-2. 12575 records from Inventario avifaunístico de las áreas focales Zoh-Laguna y La Montaña en el corredor biológico mesoamericano Sian Ka'an- Calakmul, México. 523 records from Census of invasive alien plant species of Benin (West Africa) by SOS Biodiversity. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 609 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 49 records from Distribución, abundancia y selección de hábitat de especies de aves amenazadas y en peligro de extinción en los bosques de montaña de Chiapas. 53 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 1469 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 18 records from Herpetos de un Área Degradada por Actividad Minera en la Costa Caucana. 220 records from Estado de salud y estatus de conservación de la(s) población(es) de totoaba (Totoaba macdonaldi) en el Golfo de California: una especie en peligro de extinción. 114 records from Total foraminifera counts of multinet M33/1_MSN1028. 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 529 records from Flesh Flies (Sarcophagidae) of Ireland. 61 records from Coccolith counts of multinet SO119_MSN1281. 21 records from Vogelwelt im Europa-Rosarium. 15 records from Meiofauna abundance in sediment core 54301-010. 298 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 191 records from Steinbruch Mainz-Weisenau, 2. Jahr. 179 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 10 records from Oberservation of birds at station PS14/149 along 49° West. 120 records from Total foraminifera counts of multinet M10/2_MSN262. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 18 records from Reporte hidrobiológico Río Magdalena, Sector Las Flores. Barranquilla, Atlántico. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 713 records from Vegetación de los remanentes de bosque andino, municipio de San Francisco (Cundinamarca). 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 1386 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 347 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 278 records from Deponie Klausdorf. 25 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/088-4. 46 records from Schulgelände (Wetter). 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 20 records from Riedkanal Bötzingen. 315 records from Size of planktic foraminifera at CTD station PS55/030. 158 records from Waldstück Bremerhagen LK Bio Kl. 12. 231 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 95 records from Überschwemmungsgebiet der Wied. 52 records from Dinocyst assemblages of site HM52-43. 318 records from Size of planktic foraminifera at CTD station PS55/018. 3271 records from Birds (GMBO-BI). 21 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 371 records from Bannwald Burghauser Forst. 5 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 16 records from Biodiversity monitoring in Brunswick Valley Heritage Park Mullumbimby. 12 records from Flora und Fauna am Mühlberg. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 89 records from Birdrace-Team_Wangerooge-Friesland. 111 records from Total foraminifera counts of multinet M33/1_MSN1029. 435 records from Antarctic Krill occurrence data from Discovery expeditions. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 54 records from Waldsee. 19 records from Morphologische Daten von Natrix. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 8352 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 41 records from Liether Park (LMS), 6c. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 30 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 53 records from Schulgarten Fichteschule. 95 records from BIRDRACE accipiter hardcore birding. 1045806 records from Belgian IFBL Flora Checklists (1939-1971). 112 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 20 records from Meiofauna abundance in sediment core 13077-021. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 2247405 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 63 records from Phytoplankton abundance in surface water in 2000, Ancon, Peru. 61 records from Total foraminifera counts from M35/1_MSN1063. 227 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 53 records from Total foraminifera counts of multinet M21/5_MSN735. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 416 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 2 records from BioAcoustica: Wildlife Sounds Database. 1 records from Records of Giant Silkmoths (Saturniinae) from Vermont Collections and 2002-2007. 120 records from Macroinvertebrate groups found on deep-sea volcanic habitats in the Galapagos Marine Reserve in the Eastern Tropical Pacific Ocean: Porifera. 191 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100320. 36323 records from Biowide Species data. 21 records from Abundance of benthos infauna at station GIK23004-3. 521 records from Schanzenanlage Bergham. 5188 records from Sistema Arrecifal Veracruzano: condición actual y programa permanente de monitoreo: Primera Etapa. 48 records from Dörnberg. 98 records from Total foraminifera counts of multinet POS231/3_MSN1332. 75 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 18 records from Naturtag. 2160 records from EDP Foz Tua: Bat Habitats - Complementary Studies [2010]. 460 records from Murciélagos observados en la expedición al Río Apaporis - Proyecto Colombia BIO. 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 132 records from Plasm bearing foraminifera counts of multinet M21/1_MSN613. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 30-63 µm fraction. 7 records from SuLaMa Galidictis grandidieri occurence data. 57 records from Schulgelände SGD/Viersen. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 43 records from Total foraminifera counts from M35/1_MSN1045. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 19 records from Equinodermos de las unidades ecológicas someras Expedición Seaflower Serranilla2017 - Proyecto Colombia BIO. 2258 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 670 records from Bulau. 53 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras. 41705564 records from Artportalen (Swedish Species Observation System). 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 72 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 469 records from Pez León en Venezuela. 1 records from Karpfenteich, Klasse 6d. 170 records from Total foraminifera counts of multinet SO117_MSN1244. 108 records from Total foraminifera counts of multinet M21/2_MSN628. 157 records from Murciélagos de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 78 records from Helechos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO. 3435 records from Benthos Chirnov Basin 1986 and 2002. 820 records from Queensland Museum provider for OZCAM. 48 records from Coccolith counts of multinet SO119_MSN1288. 177 records from Spießwoogtal / Königsbruch (Fischbach). 704 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 1 records from Molche in Ruschwedel. 393 records from Dinoflagellate cyst counts on sediment core ABC26. 2423 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 96 records from Plasm bearing foraminifera counts of multinet M21/1_MSN620. 337 records from Inventario de Fauna Vertebrada de la Reserva Forestal Protectora Regional de los Cañones de los Ríos Melcocho y Santo Domingo. 95 records from Ortelsbruch - Hangmoor bei Morbach. 53 records from Plasm bearing foraminifera counts from M35/1_MSN1058. 31 records from Aves of wetlands and protected forests in Benin. 1195 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 145 records from Chronicle of Nature - Phenology of Birds of Kondinskie Lakes National Park named after L. F. Stashkevich. 380 records from Artenvielfalt der Nordsee - Helgoland. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 144 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 163 records from Steinbruch Mainz-Weisenau, 3. Jahr. 135 records from Total foraminifera counts of multinet M21/3_MSN688. 78 records from Birdrace-Die_Laufenten-Braunschweig. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 78 records from Aktion - Friedensburg Oberschule. 64 records from Monitoreo de la flora presente en el páramo del Duende. 2374 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 947 records from Erlengraben/Lipp-Tal (Östringen). 27901 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 6493 records from Status, distribución, ecología y conservación de las cotorras serranas (Rhynchopsitta pachyrhyncha y R. terrisi) en el norte de México: 3a fase. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 136 records from Total foraminifera counts from multinet M32/3_MSN957. 211 records from The interstitial subsoil fauna of the medium beach level at Sarso Beach, Red Sea (Table 3). 88 records from Teich Berlin Wuhlheide. 300 records from Ried und Sand - Artenvielfalt durch Beweidung. 49 records from Coccoliths in sediment core PS1535-8. 150 records from AKG-Gelände (Bensheim). 54 records from Biotope im Schulumfeld. 242556 records from Flora Atlas N.T.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 11 records from Fishes in the Argentine Sea from 1967 to the present time. 348 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 47 records from Total foraminifera counts of multinet M10/2_MSN238. 282 records from Radiolaria assemblage in sediment core GIK23424-3. 459 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 80 records from Förderzentrum Schmölln. 121 records from Antarctic Amphipoda. 209 records from Lebensraum Gesamtschule (Langerwehe). 938 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 77431 records from Butterflies of Ireland. 32 records from Artenvielfalt auf Zollverein. 123 records from Total foraminifera counts of multinet M21/2_MSN648. 285 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 8 records from Eichendorf Weiher Schwalbach a.Ts.. 11 records from Coccolith counts of multinet M32/5_MSN986. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 438 records from Caracterización de la avifauna en una zona delimitada entre los municipios de Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño). 401 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 3 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 16 records from Hazel Dormouse in Ireland. 1118 records from ABC event data for Nyika Plateau, Buma Hills. 51 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 3 records from Blankenfelder See. 27433 records from ForestCheck Invertebrates. 4 records from The Fungal Collection at the Botanische Staatssammlung München. 36 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 46 records from An der Ohm, (Wettsaasen). 121 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 10 records from Anfibios y reptiles del municipio de Cuetzalan del Progreso, Puebla. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 969 records from Gurgltal (Tarrenz). 91 records from Radiolaria assemblage in sediment core GIK23400-3. 218 records from Migración, movimiento y distribución estacional del cachalote en el Golfo de California. 22 records from Ictiofauna Asociada a los Cativales del Municipio de Riosucio, como Aspecto Relevante dentro de la Estructura Ecológica Principal del Chocó Biogeográfico. 4122 records from (Appendix A) Abundance of benthic foraminifera in sediment core GIK17940-2. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 35 records from Ortsrand Zandershagen. 550 records from Greendale Creek and Curl Curl Lagoon Bird Survey 2017 to 2019. 17 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 610 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 505 records from National Frog Survey of Ireland 2010/2011. 142 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction >150 µm. 1 records from Streuobstwiese Alt Necheln. 2996 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 88 records from Total foraminifera counts from M35/1_MSN1065. 1333 records from Marine Turtles. 11961 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 5642 records from REDIT 1. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 4 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 117 records from Total foraminifera counts of multinet M21/2_MSN627. 416 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 289773 records from Dry Tortugas Reef Visual Census 2010. 547 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 1640 records from Implementación del Programa de Monitoreo del Cocodrilo de Pantano (Crocodrylus moreletti) México-Belice-Guatemala en la Región de Coordinación MXRC3-Sur: sur de Veracruz, Tabasco, Chiapas y oeste de Campeche. 26 records from Caracterización Ecológica de la Ornitofauna del Humedal Costero Obregón. 40 records from Total foraminifera counts of multinet M21/4_MSN716. 41 records from Total foraminifera counts of multinet M21/4_MSN714. 168 records from EPOS3: SeaStars (Echinodermata, Asteroidea). 5701 records from Gillnet test fishing and radiocaesium (Cs-137) of brown trout (Salmo trutta) and Arctic char (Salvelinus aplinus) 2008 and 2009 from 20 Central Scandinavian lakes: Occurrences. 1 records from Lizard Island Research Station. 29 records from Naturerfahrung. 60 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 5 records from Distribution ashore and breeding places of southern elephant seals. 234 records from Artenvielfalt der Nordsee - Sylt. 12 records from Kinderwald Hannover. 203 records from Total foraminifera counts from M35/1_MSN1047. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-098. 2504 records from Inventory of plant species through Benin (West Africa). 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 47 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 338 records from Unser Schulgelände. 138 records from Total foraminifera counts of multinet M12/3_MSN535. 198 records from Data on agroforestry plant species of Benin. 1553 records from InboVeg - Amphibious vegetation of shallow lakes at Turnhout. 2914 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejo de Páramos Frontino-Urrao y Citará. 142 records from Birdrace-Alte_Socken-Cuxhaven. 70 records from Total foraminifera counts of multinet M21/5_MSN731. 156 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 5621 records from Plan d'Aménagement participative de la Forêt Classée d'Alédjo (Togo). 26 records from Caracterización ecológica de la comunidad de herpetos de la ciénaga La Honda, Tanguí. 12 records from Ohemoor (Hamburg/Norderstedt). 17 records from Benthic macrofauna abundance of sediment core 13078-013. 9884 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 5 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 199 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 1816 records from SPC CoFish Invertebrates Observations Cook Islands 2007. 22 records from Análisis ecológico de la fauna en las fuentes abastecedoras de agua para comunidades indígenas de Osbezcac en la cuenca del rio Saija, Timbiquí - Cauca. 1905 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 2398 records from University of Amsterdam (NL) - Páramo vegetation research, Central Andean Cordillera - Colombia. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 663 records from Benthic foraminifera counts of sediment core GIK23352-3. 81 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 234 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 49 records from NSG Hellbachtal. 1915 records from Deforestación y fragmentación del hábitat: consecuencias ecológicas sobre la fauna de mamíferos de la selva tropical estacional. 2089 records from Benthic foraminifera of sediment core MD99-2286. 115 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 38 records from Caracterizacion de Reptiles del Cerro de Chageradó, Frontino- Antioquia). 28 records from Hainbachtal bei Oelsnitz / V.. 1 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 77 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction 63-150 µm. 164 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 144 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 33 records from Waldstück am Schullandheim Bad Bederkesa. 205 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 18 records from Schulgarten der Gesamtschule Am Heidberg. 22 records from Coccolith counts of multinet SO119_MSN1272. 162 records from Schulhof Gymnasium Hürth Bonnstrasse. 68 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 584 records from Registro de murciélagos del Cañón del Chicamocha, Santander (2013 - 2014). 174 records from BIRDRACE Bon(n)apartemöwen. 1540 records from NatureMap Calcrete Survey. 33 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1329. 3794 records from Abejas (Hymenoptera: Apoidea: Anthophila) en un bosque seco tropical del Parque Natural Regional Los Besotes, Valledupar - Cesar, Colombia. 3676 records from NatureShare. 140 records from Planktic foraminifera counts at CTD station PS55/019. 61 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 180 records from Microzooplankton abundance measured on water bottle samples at station PS58/108-1. 19 records from Landesgartenschau. 62 records from Total foraminifera counts of multinet M21/4_MSN705. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 1286 records from Conservación de la guacamaya verde (Ara militaris) en la Reserva de la Biósfera Tehuacán-Cuicatlán, México: un estudio de abundancia y reproducción en la zona de la cañada. 393 records from Heinersdorfer Sumpfwiese. 5 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 238 records from Naturerlebnisraum Koppelsberg. 10 records from UCM Vertebrate Observations Collection (Arctos). 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 3277 records from Seabird Observations, Storm Bay, Tasmania, Australia, 1991-1994. 144 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 274 records from Bernhardsthal. 125 records from Naturschutzgebiet Müchelholz (Mücheln). 166 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 163 records from Wiese am Waldrand (Gurtweil). 58 records from Relative abundance of live benthic foraminifera of sediment core M5/2_98MC. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 173 records from Renaturierung Werse (Innenbereich Beckum). 99 records from Total foraminifera counts of multinet SO118_MSN1267. 21 records from Mastofauna presentes en la ciénaga de Guineo, Riosucio, Chocó. 126 records from Total foraminifera counts of multinet M21/2_MSN651. 5 records from Vegetable Germplasm Occurrence. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 6990 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 53 records from Bad Bodenteicher Heide. 991 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 88 records from Ober-Olmer Wald 09. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 2390 records from The Fish Sampling at Lata Fish Market in Temotu Province, Solomon Islands. 103 records from BIRDRACE Resopal-Darmstadt-Dieburg. 15 records from Regenwasserabfangsbecken (Erlenbach). 6 records from Observation of birds at station PS14/152 along 49° West. 299 records from Situación actual de ocho especies de anfibios en categoría de riesgo en Veracruz. 368 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 13 records from Lepidurus arcticus survey Northeast Greenland 2013. 151 records from VSN-Wiese. 233 records from Umgebung der Gesamtschule Winterhude (Hamburg). 1975 records from Monitoreo y morfometría de la avifauna de la Universidad del Valle 2011-2012. 2009 records from Local BioBlitz Challenge 2013. 6 records from Ökosysteme rund um Wedel. 209 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 186 records from Monitoring the dynamics of a medicinal tree species Haematostaphis barteri Hook. F. in Benin. 17 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, >125 µm fraction. 322 records from Triebesbach (Zeulenroda-Triebes). 76 records from BIRDRACE Nachtigallen. 3814 records from Restauración experimental de un popal invadido por el zacate alemán (Echinochloa pyramidalis, POACEAE) en el sitio Ramsar No. 1336 La Mancha y El Llano. 145 records from Abundance of radiolaria at station LV28-66-1. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 323 records from Size of planktic foraminifera at CTD station PS55/083-1. 96 records from Wiese und Weide am Waldrand von Gusterath. 455 records from Unna-Mühlhausen, Wiesen. 510 records from IBF Monitoring of Plant Galls. 31 records from Schulaktion des Dienzenhofer-Gymnasiums. 370 records from Size of planktic foraminifera at CTD station PS55/051. 1 records from Herpetofauna de la región El Huizache, San Luis Potosí. 16 records from Benthic macrofauna abundance of sediment core 13200-008. 331 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 12 records from (Table T6) Relative abundance of Cretaceous plant microfossil taxa of ODP Site 188-1166. 31014 records from River Biologists' Database (EPA). 63099 records from CABI Africa Invasive and Alien Species data. 150 records from Selztal bei Friesenheim. 32608 records from Banded Iron Formation and Greenstone survey data. 133 records from Total foraminifera counts of multinet M10/2_MSN319. 4625 records from Tiroler Landesmuseum Ferdinandeum. 36 records from Mamíferos pequeños y grandes observados en la expedición al Río Apaporis - Proyecto Colombia BIO. 67 records from Tongrube bei Hettstedt. 4 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 30 records from Abundance of benthos infauna at station POS128/2_258. 30 records from Evaluación de la situación de Tillandsia mauryana en el Apéndice II de la CITES, según su estado de conservación y comercio. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 112 records from Birdrace_Die_Borner-Viersen. 661 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 522 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 332 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 26 records from Murray-Darling Basin waterbird survey. 66 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 95 records from Landschaftspark St.Leonhard-Deisendorf. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 16 records from Benthic macrofauna abundance of sediment core 13077-070. 1117 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 553 records from Coccolith abundence from sediment core GeoB1028-5. 28904 records from observe_tuna_bycatch_ecoscope. 214 records from Pflanzen und Tiere im Burgwald. 41 records from Örtzemündung (Stedden). 14 records from Dinámica poblacional de la tortuga de carey (Eretmochelys imbricata) en su área de forraje. Río Lagartos, Yucatán. 25 records from Heavy minerals of sediment core PL94-08. 5662 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 183 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto129-136. 100 records from Nanoplankton abundance at station GeoB2006-4. 374 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 36 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/014-4. 92 records from Schulgarten Zinnowwald-Grundschule. 12996 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves de los Complejos de Páramos de Sonsón y Urrao. 23 records from Ackerrain Plönhagen. 2 records from Coccoliths in sediment core PS1529-8. 149 records from Schiller Gymnasium Hof 10b. 488 records from Biologische Station im Kreis Wesel. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 22 records from Bachabschnitt der Nette (Osnabrück). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 162 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 313 records from BIRDRACE Gätkes Erben. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 1050 records from Fish (KIWE-PI). 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 214 records from Total foraminifera counts of multinet M21/1_MSN608. 37 records from Liether Park 2 (LMS), Klasse 6c. 1087 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 103 records from BIRDRACE federleser. 109 records from BIRDRACE Die Borner. 4 records from Microplankton abundance at bottle station SEPT-1999-K6. 262 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 96145 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 256 records from BIRDRACE Upupa epöpse. 70 records from Plasm bearing foraminifera counts from M35/1_MSN1059. 597 records from Greenland macrobenthos 2006. 458 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 7232 records from B-BLOOMS2. 47 records from Trockenrasen bei Dörndorf. 2675361 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 7922 records from Wikiplantbase #Toscana. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 42 records from Schulgarten Paul-Schneider-Schule, Münster. 176 records from A geographic distribution database of the cassava whitefly complex (Hemiptera, Aleyrodidae) and their associated parasitoids and hyperparasitoids (Hymenoptera). 348905 records from BioFokus. 2413 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 6822 records from Anymals+plants - Citizen Science Data. 16970 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 24 records from Tauchen und Meer. 64 records from Rechts des Inn Höhe Hofau Rosenheim. 1716 records from EDP Foz-Tua: Large and Medium-sized Mammals (point counts): Complementary Studies [2009-10]. 151589 records from Vogeltrekstation (NL) - Historical Data on Timing of Ringing of Nestling Birds. 3 records from Biological data from the Soviet Antarctic Expedition (1955-1958). 26 records from Aves marinas de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 74 records from Total foraminifera counts of multinet M21/4_MSN699. 114 records from BIRDRACE Di-Bi-Di-Birder. 3560 records from Relative abundance of planktic foraminifera in sediment core GeoB1309-2. 176 records from BIRDRACE Professorenteam. 364 records from "Tre Pini" (Montebelluna, Italien). 134 records from Birdrace-Easy_Birders-Plön. 1949 records from Large herbivores in African savannahs, Lake Mburo National Park, Uganda. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 204 records from Total foraminifera counts of multinet SO118_MSN1253. 59 records from Im Bauerngarten. 39 records from Streuobstwiesengelände St.Meinrad Gymnasium. 47 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 1508 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 235 records from Pseudoscorpions of Ireland. 10 records from Ice Amphipods Canada Basin. 15754 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 167 records from Total foraminifera counts of multinet M21/6_MSN776. 199 records from Microzooplankton abundance measured on water bottle samples at station PS58/049-3. 4 records from Wälder und Seen rund um den Mühlenberg. 233 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/045-9. 111 records from Plasm bearing foraminifera counts from M35/1_MSN1065. 957 records from Mamíferos de 14 municipios del Departamento del Valle del Cauca para el fortalecimiento de RNSC y Caracterización de Predios Adquiridos para la Conservación de Cuencas. 302 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 35 records from Plasm bearing foraminifera counts of multinet M21/5_MSN736. 96 records from Especies silvestres de nopales mexicanos. 10 records from Benthic macrofauna abundance of sediment core 12930-093. 128 records from Streuobstwiese Kattenhund (Schleswig). 18 records from Registros de anuros presentes en los Páramos de Santurbán, Rabanal y Las Hermosas. 153 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 42 records from SuLaMa reptile survey 2013. 136 records from Planktic foraminifera counts at CTD station PS55/080-1. 54 records from VFD-H: MIttelgebirgsweide. 329 records from Assemblage of living benthic foraminifera in sediment core GeoB3712-1. 165 records from Weidenhüttendorf an der Würm (München). 51 records from Total foraminifera counts from M35/1_MSN1052. 561 records from Liste d'espèces animales recensées au cours des activités de l'Organisation pour le Développement Durable et la Biodiversité (ODDB ONG) au Bénin. 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 103 records from Total foraminifera counts from M35/1_MSN1044. 149 records from Total foraminifera counts of multinet M21/3_MSN675. 38 records from BB-Biodiversität a. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 2204 records from Área Galeras - Monitoreo de Aves, 2017. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 2626773 records from FLORIVON. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 37 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/092-3. 220 records from Phytoplankton from Ghana. 140 records from BIRDRACE Guckers Offenbach. 84 records from BIRDRACE Bielefinken. 44 records from Phytoplankton abundance in surface water in 1997, Ancon, Peru. 115 records from Mamíferos de los Parques Ecológicos Distritales de Humedales de Bogotá, D.C.. 145 records from Abundance of radiolaria at station LV28-29-1. 44 records from Flusswerder in der Weser (Hameln). 111 records from Caracterización de Flora de la Reserva Forestal Protectora Regional Brisas del Rincón. 176 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 23 records from Schulgarten der Hainbuchenschule (Hagenbach). 1102 records from Plantas laguna El Tinije. 40 records from Plasm bearing foraminifera counts of multinet M21/5_MSN733. 59 records from Schulhofuntersuchung Thomas-Mann-OS. 8 records from Die Bachspezies 2008/2009. 123 records from Birdrace-SportfreundeTriller-Münster. 68 records from Streuobstwiese. 23 records from Abundance of benthos infauna at station GIK23042-2. 43 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 130 records from BIRDRACE - The famous Grouse feat. The James. 54 records from Plasm bearing foraminifera counts of multinet M21/2_MSN629. 48 records from Junge Heide, Radebeul/Dresden. 1709 records from The Gibson spider collection. 99 records from Naturgrundstück (Eutin). 193 records from Truppenübungsplatz Panzerkaserne Böblingen. 1811 records from Peces batoideos de la plataforma continental del Golfo de Tehuantepec. 7708 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 185 records from Estado actual de la distribución de los anfibios y reptiles de la Región de Los Tuxtlas. 684 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 181-1119. 3669 records from ARKO strandeng. 140 records from Abundance of planktic foraminifera at CTD station PS55/019. 290 records from (Fig. 6, 7) Aragonite preservation of sediment core GeoB2204-2. 97 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 12 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán (continuación). 6 records from MVZ Herp Observations (Arctos). 245 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 1544 records from National Whale and Dolphin Sightings and Strandings Database. 40 records from Plants Of The Green Line - Woolsthorpe Section. 20 records from Comunidad de Reptiles presentes en el Cerro Jánano. 229 records from Vorderer Tiergarten (Dessau). 22701 records from Restauración y conservación de Isla Guadalupe. 12 records from Kindergarten. 96 records from Warnowtal (Rostock). 2493 records from Rasgos funcionales de plantas, anfibios y aves estudios bióticos complejos de páramos Chiles - Cumbal, La Cocha - Patascoy, Doña Juana - Chimayoy. 930 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 6 records from Wuhle - Brücke / B1. 175470 records from Florida Keys Reef Visual Census 1999. 8 records from Benthic macrofauna abundance of sediment core 12930-068. 108 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 109 records from iHerbarium. 755 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 40 records from Abundance of benthos infauna at station GIK23013-2. 111 records from BIRDRACE Die Wendehälse. 55 records from Mauervegetation,Flechten und anderes. 264 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 281 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 73 records from In situ observations of Stygiomedusa gigantea. 10 records from Antarctic Krill occurrence data from Japanese expeditions. 241 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto120-128. 656 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 156 records from Bizzenbachtal (Wehrheim/Taunus). 19297 records from Irish Crop Wild Relative Database. 227 records from Klutensee. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 1 records from Molluscan fauna of Gueishan Island of Taiwan. 327 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 37 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core BMR96GC21 in the southeast Indian Ocean. 551 records from La ballena jorobada, Megaptera novaeangliae, en la Península de Baja California Sur, México. 550 records from Radiolaria assemblage in sediment core GIK23414-6. 26681 records from Seasearch Marine Surveys in England. 129 records from Plasm bearing foraminifera counts of multinet M21/2_MSN657. 1221 records from Siliceous microfossil occurrence, Site 177-1088. 61 records from BIRDRACE Kollektiv Eisente. 160 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 2377 records from Invasive Alien Species Occurrence in Ghana. 42221 records from CCAMLR historic KRILL. 176 records from Isotope age and relative abundance of planktonic foraminifera in Core Vulk-34-90, Sea of Okhotsk. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 242 records from Quarrendorfer Landschaftsschutzgebiet. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 53 records from Relative abundance of planktic foraminifera in sediment core K11. 11 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 105 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 1825 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 36 records from The nematoda fauna of sediment samples of Sarso Islands, Red Sea (Table 5). 60 records from Amtsrain Apolda-Zottelstedt. 40135 records from DIBA-Parc del Montnegre i el Corredor. 4759 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 112 records from Werl macht sich auf die Suche. 117 records from GEO-Hauptveranstaltung Bodden (Vilm). 7 records from Grundwasserlebensraum im Englischen Garten (München). 1627 records from Inventario de macroalgas de Isla Guadalupe, México. 31 records from Coccolith counts of multinet M32/5_MSN974. 13 records from Meiofauna abundance in sediment core 54301-009. 58 records from Plasm bearing foraminifera counts of multinet M21/2_MSN651. 6 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 31 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 26 records from Erhard Sopp. 1486 records from Mollusc (non-marine) data for the Channel Islands. 78 records from Total foraminifera counts of multinet M21/4_MSN695. 97 records from Dorfrand Mauderode. 134 records from Abundance of planktic foraminifera at CTD station PS55/082-1. 47 records from Shrews of Poland. 3837 records from NDFF Wall Plants Monitoring Program. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 154 records from Blumenrather Heide / Virneburg. 19 records from Meiofauna abundance in sediment core 12930-075. 269 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 2 records from Wie viel Natur gibt es im Park?. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 1052 records from Aves Marinas y Playeras en el PNN Sanquianga y la Bocana de Iscuandé entre 2007 y 2009. 410 records from Aves de Caño Cristales, La Macarena, Meta. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 307 records from Umgebung der Gesamtschule Hamburg-Winterhude. 1179 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 1024 records from BUND - Dassower See (Lübeck/Dassow). 81 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres presentes en Papigochic y su zona de influencia.. 4 records from Sächsische Schweiz (Wehlener Gebiet). 171 records from Leben im Finkensteiner Moor. 53985 records from Marine sites, habitats and species data collected during the BioMar survey of Ireland.. 101 records from Birdrace-Herford-Birder-Herford. 113 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 770 records from Distribution of major planktic foraminifer at Site 177-1093. 2555 records from ConDidact Citizen Science Surveys - Spiders 2014. 25 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 94 records from Die Wuhle. 958 records from Schulzentrum "Parc Hosingen". 141 records from Pfingstexkursion Alter Bessin. 570 records from Cuxhavener Küstenheiden. 106 records from vegoek. 32 records from Grundschüler erkunden Schulumgebung. 623 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 35 records from Ice Algae Barents Sea. 83 records from Ross Sea Pycnogonids. 680 records from ConDidact Citizen Science Surveys - Ladybirds 2013. 379 records from USGS SESC - Biscayne - Herpetofauna - 2002-2003. 2286 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 451760 records from PlutoF platform observations. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 62 records from Zoo Frankfurt. 205 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 2 records from Revisión de las Agavaceae (sensu stricto), Crassulaceae y Liliaceae incluidas en el PROY-NOM-059-ECOL-2000. 326 records from Peces de las unidades ecológicas someras Expedición Seaflower Serranilla 2017 - Proyecto Colombia BIO. 170 records from Total foraminifera counts from multinet M31/3_MSN898. 13 records from Analyses of the recent components of sediment core PS1422-1. 72 records from Plasm bearing foraminifera counts of multinet M36/2_MSN1107. 1174 records from Sudeniederung (Amt Neuhaus). 209 records from Hamberger Brücke / Würmtal (Pforzheim). 18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 29 records from Hemmerder Schelk (Unna). 53 records from Artenvielfalt im Umfeld der Burgwegschule. 203 records from Total foraminifera counts of multinet M21/1_MSN604. 198152 records from IBF Monitoring of Vascular Plants. 1850 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 117 records from Naturschutzgebiet Lochbusch-Königswiesen. 272 records from BIRDRACE Niederlausitz-Team. 148 records from Schulgarten Huttenheim (Philippsburg/Baden). 106949 records from The CPR Survey. 256 records from Vocalizaciones de aves mexicanas en análisis biogeográficos y reconstrucción filogenética. 311 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 31 records from Bayerische Donau - Tapfheim. 381 records from Priority effects of early successional insects influence late successional fungi in dead wood. 3555 records from Epibenthos and demersal fish monitoring in function of dredge disposal monitoring in the Belgian part of the North Sea. 157 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 266 records from Registros de flora de las caracterizaciones rápidas de coberturas en los municipios de Beltrán y Guataquí, Cundinamarca. 217 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 7 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 148 records from Total foraminifera counts of multinet M21/1_MSN611. 280 records from Faberpark (Nürnberg/Stein). 227 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 762 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 7 records from ECOLINC: BIODIVERSITY OF THE WESTERN VOLCANIC PLAINS SIGHTINGS. 149 records from Nanoplankton abundance at station GeoB2012-2. 493 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 11693 records from Database for alien invasive plants occurrences in Germany. 710 records from Benthic foraminifera distribution of sediment core BP01-62/06. 1179 records from Evaluación y monitoreo de manglar en la Reserva de la Biósfera Los Petenes con énfasis en criterios de sustentabilidad y desarrollo. 113 records from Tornoer Teich. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 68 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 138 records from Fish Collection Ismael Kong, Universidad de Antofagasta, Chile. 170 records from Abundance of calcareous dinoflagellates of sediment core GeoB3603-2. 2333 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 2017 records from Flore des reliques forestières de la commune de Dangbo. 143 records from BIRDRACE Die Laufenten. 217 records from Microzooplankton abundance measured on water bottle samples at station PS58/088-4. 26 records from Abundance of benthos infauna at station GIK23046-1. 12 records from Peces de la cuenca alta y media del río Bita, Vichada (Colombia). 103540 records from Florida Keys Reef Visual Census 2006. 604 records from Ecología y manejo de ungulados cinegéticos en el sur de Baja California Sur. 16891 records from Global Lacustrine Diatoms. 83 records from VFD-H: Heidenrod: Pferdeweide Mürth. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 1768 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 405 records from Catch related distribution of Appendicularia at station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 7). 80 records from Total foraminifera counts from multinet SO119_MSN1303. 120 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 1357 records from Ostracoda in sediment core PS51/154-11. 185 records from Total foraminifera counts of multinet M21/2_MSN657. 91 records from Nottekanal, Klasse 7 - 10. 29 records from Waldwiese. 8072 records from Riqueza específica, distribución y abundancia de aves acuáticas en la ensenada de La Paz, Baja California Sur, México. 3685 records from Clare Biological Records Centre Dataset 2004-2007. 1409 records from Diatom assamblage in samples from sediment trap OG5. 573 records from Caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 168 records from Wanderweg am Windebyer Noor (bei Eckernförde). 50 records from Flora und Fauna im Brexbachtal. 1 records from Sungei Buloh - Mangrovenwald. 190 records from Herpetofauna laguna El Tinije. 91 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 123 records from Birdrace-Professorenteam-Münster. 6140 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 98 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 44 records from Total foraminifera counts of multinet M27/2_MSN879. 131 records from Planktic foraminifera counts at CTD station PS55/083-1. 336 records from (Table S1) Dinoflagellate cysts, pollen and spores of sediment core ABC26. 1597 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 146 records from Steinbruch Mainz-Weisenau. 60 records from Hochschule Zittau/Görlitz. 18 records from Meiofauna abundance in sediment core 12930-029. 40174 records from SBC LTER Darwin Core Archive: Kelp Forest Reef Fish Abundance. 121 records from Total foraminifera counts of multinet M12/3_MSN557. 715 records from Fauna y flora del municipio de Lipa, Arauca. 586 records from (Table 3h) Foraminiferal distribution chart of petroleum well Swan-3St. 28 records from Nationalpark Harz Schul-AG Braunlage. 6847 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 23 records from AKG-Gelände in Bensheim. 2346 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 38 records from Was lebt in der Brutzwiese?. 3 records from Biodiversity Surveys, South-east Arnhem Land. 39 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 167 records from Birdrace-Nord_Seh_Team-Nordfriesland. 14 records from Benthic macrofauna abundance of sediment core 13200-045. 1879 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 1029 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 1470 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 101 records from Fuchsloch (Mohlsdorf/Ostthüringen). 2336 records from (App 8) Relative contents of planktonic foraminifera species in sediments from Core GeoB3011-2. 108 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 83 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 49 records from VFD-H.: Rheingau: Bärstadt. 391 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 159 records from Inventario de invertebrados marinos del SFF Isla Malpelo, Proyecto Colombia BIO. 99 records from Streuobstwiese Stedar. 1343 records from Plymouth sound dataset. Soft sediment macrobenthos from the Plymouth Sound from 1995. 14 records from Relative abundance of live benthic foraminifera of sediment core M5/2_91MC. 141 records from Caracterización ambiental del complejo cenagoso La Larga, Tagachí, Chocó. 4 records from Echinoderms from the Seaflower Biosphere Reserve. 5851 records from Dénombrement des oiseaux d'eau du Sénégal de 2016 à 2018. 1056 records from Diatom assamblage in samples from sediment trap OG4. 27 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 175 records from Pine Marten (Martes martes) Database (NPWS). 224 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 40 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 13 records from Distribution of meiobenthos in sediment core M23_203 of the northeastern Atlantic (Table 1). 60 records from Rotes Steigle (Panzerübungplatz Böblingen). 145 records from Gronau - auf der Suche nach dem Neunauge. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 1643 records from SPC PROCFish/C Invertebrates Observations New Caledonia 2003 to 2008. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 69 records from Entdeckertour am Muldestausee 1/05. 30 records from Antarctic and sub-Antarctic Lophogastrida occurrences. 4 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 53 records from Plasm bearing foraminifera counts of multinet M21/5_MSN740. 77 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 363 records from Fauna y flora de la cuenca media del río Lebrija en Rionegro, Santander. 108 records from BIRDRACE Diesmal sehen wir mehr. 1352 records from Saproxylic insects caught in window traps and hatched from polypores in small and large old forests in southern Norway. 315 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 10 records from Benthic macrofauna abundance of sediment core 12930-095. 201 records from Total foraminifera counts of multinet M21/3_MSN663. 260 records from Artenvielfalt Kreis Gießen. 220070 records from Florida Keys Reef Visual Census 2000. 91 records from Birdrace-Enger_am_Spektiv-Herford. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 973 records from Biogeographic distribution of the Antarctic and Sub-Antarctic brachiopods (living forms). 678 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 62 records from nnf_verdisetting_vestlandet. 201 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 29 records from Winter Foraging Locations Of Southern Ocean Predators - sub-Antarctic islands 2008/09. 4 records from Microplankton abundance at bottle station SEPT-1999-K7. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 66248 records from Atlantic and Gulf Rapid Reef Assessment - Benthic. 215 records from Umgebung der Grundschule Oderberg. 473 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 1618 records from Ganadería Colombiana Sostenible (escarabajos coprófagos 2017). 4251 records from Aves de la cuenca media del río Chambery, Caldas. 274 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 72 records from Antarctic Parborlasia corrugatus. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 45 records from Abundance of benthos infauna at station POS128/2_281. 4176 records from Badger and Habitats Survey of Ireland. 636 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 209 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 724 records from Heritage Trees of Ireland. 42 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 8058 records from ZooplanktonBeaufortSeaNOGAP1. 73 records from VFD-HH/SH: Pferdweide Lammert. 429 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 34 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 441 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core A180-073. 14125 records from imr_mareano_rpsledge. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 186 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 50 records from Leben in den Elbwiesen. 211 records from Binsenwiesen. 399 records from Gola National Park Biomonitoring Data. 310 records from Geelong Field Naturalists Club. 706 records from Zukünftiges NSG Höftland/Bockholmwik. 23 records from Abundance of benthos infauna at station GIK23055-1. 2269 records from Invasive species - Fallopia japonica on river dikes along the river Zeeschelde, Rupel and Durme. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 318 records from Línea base del medio biótico en los bosques para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguablanca -El Morro Yopal. 22 records from Planktic foraminifera of sediment core GeoB1407-2. 10 records from Benthic macrofauna abundance of sediment core 13200-017. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 288 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 13 records from Registro Herpetofauna de los Corregimientos de Juanchaco y Ladrilleros, Municipio de Buenaventura (Valle del Cauca) Septiembre de 2016. 2412 records from Inventaire des espèces végétales dans le cadre de plusieurs études menées au Sud-Bénin. 5 records from Regenwasserabfangbecken Erlenbach. 2 records from Kirchenforst. 4300 records from Census of plant species of Benin (West Africa): Database4. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 5625 records from RAVON (NL) - Network Ecological Monitoring Reptiles. 148 records from Abundance of radiolaria at station UT99-21-2. 324 records from Alterra (NL) - Microarthropods inventory in Heathland. 314 records from Peces laguna El Tinije. 119 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 2 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 118 records from BIRDRACE Die Lippegeier. 148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 13 records from Comunidad de macroinvertebrados acuáticos presentes en fuentes abastecedoras de agua en La sierpe - Osbezcac (rio Saija, Timbiquí - Cauca). 44 records from Antarctic Starfish (Echinodermata: asteroidea) from the ANDEEP3 expedition. 94 records from Nationalpark Jasmund. 109 records from Exkursion Ebertsheimer/Grünstädter Berg. 75 records from BIRDRACE Die Kartoffelsäcke. 43 records from Vogelstimmenführung durch den Tiergarten. 2 records from Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2010) - sensitive records. 244 records from Schule Sulzbach (Oberegg). 69 records from Evaluación de la presencia de 'Marmosa robinsoni' e inventario de mamíferos en el Departamento del Atlántico. 28 records from Mammals (NSMK-MM). 80 records from BIRDRACE Falkenberger Fluppis. 483 records from Artenvielfalt im Rhein-Neckar-Raum. 280 records from Distribution of foraminifera of sediment core GK_32_C. 1043 records from The Ecology of the Inshore Marine Zooplankton of the Chukchi Sea near Point Barrow, Alaska. 51 records from Relative abundance of live benthic foraminifera of sediment core M5/2_93MC. 31 records from Aktionstag Wiese am Vogelhammerkopf. 98 records from Total foraminifera counts from M35/1_MSN1067. 41 records from (Table 3a) Distribution of planktonic foraminiferal tests in sediments from Core NKA-37T. 90 records from Plasm bearing foraminifera counts from M35/1_MSN1045. 139 records from Schulhof und Anlagensee in Nellingen. 39471 records from Monitoreo Ambiental del Proyecto La Colosa. 16 records from Im und um das Schulhaus. 121 records from Meiobenthic assemblages colonizing artificial soft sediments at 20 m depth in Arctic glacial Kongsfjorden, Spitsbergen, Svalbard - individual number. 96 records from BIRDRACE OAG Neuwerk. 34 records from Selz (Ingelheim am Rhein). 180 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 3 records from Benthic foraminifera abundance of Hole 96-621. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 57 records from Kindervilla Aussengelände/ Hiltroper Park. 1012 records from Inventario de los crustáceos decápodos asociados al ecosistema coralino de Pocillopora en el Pacífico tropical mexicano. 773 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México. 5 records from Plasm bearing foraminifera counts from M35/1_MSN1055. 308 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 54 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996.. 23 records from Coccolith counts of multinet M32/5_MSN977. 168 records from Canada_BasinMegabenthos2002. 1 records from Fungal Records Database of Britain and Ireland. 28 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC464. 1 records from LUNG-Naturwiese. 543 records from SPC PROCFish/C Fish Observations Fiji 2002-2003. 150 records from Total foraminifera counts of multinet M21/2_MSN643. 139 records from Caracterizacion florística del Cerro de Chageradó (Frontino- Antioquia), 2011. 7 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 421246 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 192 records from "Ahrschleife bei Altenahr". 96 records from (Table 2) Sea surface temperature reconstruction from sediment core MD88-770. 2 records from South Australian Museum Australia provider for OZCAM. 35 records from Urwald 3 (Bad Waldsee). 35 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 5 records from Coccolith counts of multinet M32/5_MSN981. 909 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 6784 records from Whicher Scarp Flora Survey. 404817 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 69 records from Unter hellen Zinnen und finsteren Grotten. 121 records from BIRDRACE Immerwiederhopf. 34 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 129 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0011B. 37 records from Caracterización de Reptiles de las lagunas del municipio del Medio Baudó. 348 records from Coastal and Marine Species Database. 50 records from Caracterización de la ornitofauna del Cerro Tacarcuna, Unguía, Chocó. 6 records from Reporte de Anfibios presentes en los corregimientos de Juanchaco y Ladrilleros (Buenaventura, Valle del Cauca) para el mes de septiembre de 2017. 121 records from 4. GEO-Tag in Eberbach. 54 records from Weidegebiete in der Selzrenaturierung. 3994 records from GEO-Hauptveranstaltung in "Wildtierland". 744 records from Ostracoda in sediment core PS51/159-10. 102 records from Raus in die Natur. 5 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, >125 µm fraction. 1811 records from Point Count Data for TIDE's Private Land (Kern), Belize 2009-2013. 383 records from Insectos asociados a tres ventanas de la Orinoquia Colombiana - SULU I. 45 records from BIRDRACE Ohne Graureiher läuft nix!. 55 records from Seeufer ehem. BUGA-Gelände. 912 records from CMarZ (Census of Marine Zooplankton)-Asia Database. 1045 records from kerkyra. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 68 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 91 records from Census of invasive alien and threatened species plants of Benin. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 225 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 15615 records from Point Count Data for Chaa Creek Lodge, Belize 1997-2001. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 29 records from Brenz (Heidenheim). 232 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 134 records from Total foraminifera counts of multinet M21/6_MSN785. 3171 records from SO-Polylist. 1021 records from Registros Primates Neotropicales Convocatoria APC. 4031 records from Benthic foraminifera distribution of sediment core GIK17957-2. 124 records from Total foraminifera counts of multinet M10/2_MSN317. 19 records from Benthic macrofauna abundance of sediment core 13200-004. 53 records from BIRDRACE Taubenhaucher. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 269 records from BIRDRACE Kosmos-Racer. 25 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 31 records from Kurler Busch (Scharnhorst). 369 records from BIRDRACE Havelland. 2126 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 135 records from Birdrace_Dith_MarshSandpiper-Dithmarschen. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 50 records from Inventario florístico en la zona de Bahía Magdalena e islas adyacentes, Baja California Sur. 373 records from Otter survey of Ireland 2004 & 2005. 84 records from BIRDRACE Vogelscheuchen. 2287 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 81 records from Birdrace-Die_Ornithomaten-Herford. 902 records from Área Galeras - Monitoreo de Aves abril-octubre, 2018. 87 records from Mammals (UWEP-MM). 84981 records from NINA Vanndata fisk. 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 159 records from VFD-BW, Oberrhein/Schwarzwaldrand: Pferdeweiden Liel. 10 records from Working on Country Indigenous Ranger Program. 36 records from Salzwiese Diekskiel. 23 records from Landwehrbach. 597 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 186 records from SIM-XII Jornadas Micológicas El Ilustre Minero. 29 records from Birkenpilz. 136 records from Abundance of planktic foraminifera at CTD station PS55/018. 62 records from Artenvielfalt in der Kinderakademie im RFZ. 61 records from Alien Species in Poland - Plants. 1276 records from Pollen analysis of Site 175-1075 (part 1). 50 records from Weidegut Rechab. 1197 records from Waarneming.nl (NL) - Great Grey Shrike Count 2014-2015. 979 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 35 records from Total foraminifera counts of multinet FCA97C_MSN1339. 50 records from Tití Gris (Saguinus leucopus) en remanentes de bosque de los departamentos de Caldas y Antioquia. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 47 records from Freiheitsring (Frechen). 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 19294 records from New Zealand Biodiversity Recording Network. 1437 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 97 records from Avifauna asociada a las fuentes abastecedoras de agua en La sierpe - Osbezcac (rio Saija, Timbiquí - Cauca). 5721 records from Underwater fish visual census in the Azores from 1997 to 2015. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 163 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres en La Chinantla. 118 records from Total foraminifera counts of multinet POS231/3_MSN1329. 134 records from Birdrace-Team_Havelland-Havelland. 32 records from Sizing Ocean Giants. 341 records from Carnarvon Basin wetland survey. 89963 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 140 records from Abundance of radiolaria at station UT99-4-2. 211 records from Prophetensee Quickborn. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 265 records from Luderbusch. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 168 records from Die Teiche im Britzer Garten. 797 records from Área Galeras - Monitoreo de Aves, 2016. 2056 records from Collections data on ecology of bottom animal of the Southern ocean. 425 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 1659 records from Weddell Seal Sightings, Vestfold Hills, Antarctica. 655 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 134 records from Total foraminifera counts from M35/1_MSN1046. 20 records from Heavy minerals of sediment core PL94-64. 1405 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 7136 records from Ravensthorpe Range survey data. 5 records from Schulinnenhöfe (Gelsenkirchen). 157 records from Wirbach-Taubental (Bad Blankenburg). 48 records from Plasm bearing foraminifera counts of multinet M21/5_MSN741. 497621 records from Fauna Atlas N.T.. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 31 records from Nanoplankton abundance at station GeoB2012-5. 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 131 records from BIRDRACE Brut. 45 records from Total foraminifera counts of multinet M21/4_MSN719. 24 records from Planktic foraminifera assemblage in sediment core GIK23066-2. 99 records from Wikiplantbase #Sicilia. 162 records from Antarctic fish Gobionotothen gibberifrons. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 48 records from Foraminifera and stable isotopes of sediment core PS2076-1. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 2744 records from Distribution of major planktic foraminifer at Site 177-1090. 359 records from Pöhlberg bei Annaberg. 29 records from Abundance of benthos infauna at station POS128/2_284. 64 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 453 records from Distribución e inventario de algunas especies bentónicas (hexacorales, octocorales, esponjas, y especies misceláneas) en arrecifes del Caribe mexicano. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 45 records from (Table S2) Age determination of ODP Sites 202-1234 and 202-1235. 29 records from Caracterización Ecológica de los Mamíferos del Cerro Jánano. 231 records from Total foraminifera counts from multinet M32/5_MSN976. 33 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/090-4. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 30 records from Ornitofauna de un Área Degradada por Actividad Minera en la Costa Caucana. 195 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 121 records from Birdrace_Deutschlands_enthusiast.Vogelkucker-Münster. 75325 records from The Taiwan Breeding Bird Survey Data. 16 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 63 records from Gemeinschaftsgarten Deluxe (Bernburg). 650 records from The Living Murray Fish data. 13 records from Analyses of the recent components of sediment core PS1422-1. 704 records from EDP Foz-Tua: Terrestrial Birds (point counts) Complementary Studies [2010]. 23 records from Phytoplankton abundance in surface water in 1994, Ancon, Peru. 827 records from Schatzinsel Norderney. 93 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 4 records from published Chenopodium vulvaria observations. 212 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 122 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 162 records from Total foraminifera counts of multinet M21/2_MSN658. 1 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 2857 records from Anfibios y reptiles de las regiones Chimalapas (7) y bosque de coníferas y BMM de Veracruz (11). 62 records from Kabelskebach (Kabelsketal, Saalkreis). 110 records from Pollen analysis of sediment core GeoB1007-4. 96 records from Inventario de los murciélagos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, Baja California, México. 68 records from Addenda a la colección de referencia de invertebrados de la Estación Mazatlán, UNAM y análisis de la fauna de crustáceos isópodos del Pacífico mexicano, julio 1996-julio 1997. 101 records from BIRDRACE Enger am Spektiv. 90 records from Plasm bearing foraminifera counts of multinet M21/2_MSN639. 131 records from Total foraminifera counts from multinet M32/3_MSN956. 447 records from Gelände des IVL (Zeckern). 3 records from MVZ Mammal Observations (Arctos). 13 records from Warnowufer Groß Klein. 109 records from Planktic foraminifera assemblage in sediment core GIK23056-1. 7 records from Stadtrandlandschaft Apolda-Nord. 8 records from Krittenhorster Wald (Ostkilver). 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 170 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 16 records from National census of Lepidochelys olivacea (Benin). 151980 records from Programa de Observadores a Bordo (POBCh) de la Secretaria de Pesca de la Provincia del Chubut, Argentina . Observer On board Program -Fisheries Secretariat of the Province of Chubut-Argentina (OOBPPCh). 130046 records from Florida Keys Reef Visual Census 2010. 1339711 records from EBCC Atlas of European Breeding Birds. 153 records from annex1. 130 records from Total foraminifera counts of multinet POS231/3_MSN1331. 2363 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia). 796 records from Caracterización del hábitat y patrones de distribución del gorrión serrano (Xenospiza baileyi) en el sur del Valle de México. 30801 records from Atlas of Mammals in Ireland 2010-2015. 200 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 137 records from Draubiotop Lavamünd. 245 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 136 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 384 records from "Schwarzwassertal" bei Pobershau. 217 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 20187 records from Alterra (NL) - Entomofauna inventory in riverside grasslands. 92 records from Birdrace_TerraCamper-Münster. 4515 records from Distribution of planktic foraminifera of sediment core M35003-4. 41 records from AlgaTerra. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 971 records from Danielsberg (Mölltal, Kärnten). 20 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 405 records from Censo del Zarapito Trinador (Numenius phaeopus) y Otras Aves Acuáticas en el Parque Nacional Natural Sanquianga. 34 records from Borkhart. 226 records from Planktic foraminifera assemblage in sediment core GIK17730-4. 2753 records from Seabirds of the Southern and South Indian Ocean. 18 records from Meiofauna abundance in sediment core 12930-036. 2 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 620 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 36 records from Abundance of benthos infauna at station GIK23043-2. 18 records from Fossil occurrence of planktonic foraminifera from IODP Hole 315-C0001I. 33 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/046-3. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 240 records from Landschaftspflegehof (Berlin). 9 records from Bachpatenschaft Beeke. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 167 records from SPC CoFish Invertebrates Observations Niue 2005. 84 records from Total foraminifera counts from M35/1_MSN1051. 1498 records from Gemeinde Sursee. 165 records from Artenvielfalt auf den Elbwiesen (Dessau). 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-004. 46 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras. 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 2840 records from Bases para el monitoreo de dos especies de carnívoros medianos en la Reserva de la Biosfera de Mapimí, Durango. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 191 records from Lindau im Bodensee. 189 records from Naturpark Sternberger Seenland. 3603 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 90 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 19 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 5 records from Fledermäuse u. nachtaktive Insekten. 82 records from Plasm bearing foraminifera counts of multinet M27/2_MSN883. 273 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 6 records from Mamíferos Asociados al Cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO. 1148 records from Biodiversité végétale de quelques écosystèmes au Bénin. 17 records from New contributions to the Eulophidae fauna from Morocco (Hymenoptera: Chalcidoidea) with comparison in the North African region. 260 records from Miljodir_naturtypekartlegging_2017. 243 records from WildesMoor bei Schwabstedt. 4 records from Reptilien und Insekten Entdecker / Schulgelände BBS Rotenburg. 128 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 2 records from The Erysiphales Collection at the Botanische Staatssammlung München. 9366 records from ZooplanktonBeaufortSeaNOGAP2. 294 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 154 records from Total foraminifera counts of multinet M21/3_MSN671. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 505 records from List of medicinal and agroforestry plants found in various ecosystems of Benin. 366 records from Weinberg Reichersdorf. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-084. 1508 records from Relative abundance of planktic foraminifera in sediment core GeoB1523-1. 258 records from BIRDRACE Raumpatrouille Oriolus. 103 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 84 records from "Schlechteberg" Ebersbach/Sa.. 263 records from Macrozoobenthos composition, abundance and biomass in the Arctic Ocean along a transect between Svalbard and the Makarov Basin 1991. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 27 records from Schulgarten Waldorfschule Hassfurt. 31 records from Projekt Wahner Heide. 1364 records from ACCDC: Rare Species in Atlantic Canada and Adjacent Marine Waters. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 246 records from Distribution of major planktic foraminifer at Site 177-1094. 133 records from Total foraminifera counts of multinet M10/2_MSN265. 19 records from Planktic foraminifera assemblage in sediment core GIK23246-2. 161 records from Composición y estructura de los ensamblajes de anfibios y sus posibles amenazas en coberturas vegetales en el Parque Nacional Natural Selva de Florencia. 2058 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 310 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 24 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, 63-125 µm fraction. 315 records from Caracterización florística de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 21663 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 68 records from Brachiopoda distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-078. 341 records from Nemertina World Checklist. 91 records from Kochertgraben II. 197 records from Plasm bearing foraminifera counts from M35/1_MSN1067. 9022531 records from iNaturalist Research-grade Observations. 8928 records from City of Amsterdam (NL) - Fyke Fishing Piet Ruiter. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 504 records from Dieta y preferencias alimenticias de poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en Paz de Ariporo, Casanare. 2105 records from USGS SESC - Big Cypress - Herpetofauna - 2002-2003. 4 records from Área Nevado Del Huila - Densidad poblacional especies ensamblaje de aves, 2017. 187 records from Anfibios y Reptiles asociados a tres ventanas de la Orinoquia Colombiana - SULU I. 74965 records from Mollusc (marine) data for Great Britain and Ireland. 147 records from Hintere Halde. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 31 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 208 records from Stadt Königs Wusterhausen. 1459 records from Esponjas, corales escleractinios, equinodermos y peces de arrecifes coralinos del norte y sur de Veracruz. 891 records from Atlas of Life in the Coastal Wilderness - Sightings. 6 records from Oberservation of birds at station PS14/146 along 49° West. 72 records from Tiergarten (Zeitz). 110 records from Ökologischer Weinberg (Guntersblum). 1 records from Der Kreuzenzian und sein Bläuling. 659 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 19390 records from Anfibios y reptiles de las regiones 30 (Parque Natural Sierra Maderas del Carmen); 31 (Sierra El Burro-Río San Rodrigo); 36 (Sierra La Encantada); y 37 (Sierra El Pino), Coahuila. 202 records from Wikiplantbase #Sardegna. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 64 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 66 records from Wedeler Au. 213 records from Mißmahlsche Anlage. 168 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770. 46 records from Ruhrwiesen bei Neheim-Hüsten. 5587 records from Snow Petrel nest census, Mawson region 2004/05. 271 records from ABC Matandwe Forest Reserve Vegetation Survey. 1 records from Intermountain Herbarium (Utah State University). 2 records from Hildener Heide - Spörkelnbruch (Haan). 93 records from Peces y Mamíferos de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua. 272 records from Lacewings (Neuroptera) of Ireland. 21661 records from 臺灣兩棲類資源調查與教育宣導推廣計畫 Resources survey and education advocacy to promote for Taiwan amphibian resources. 351 records from Küstenschutzwald. 4 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 134 records from BIRDRACE Griffin Wood Warblers. 12 records from Distribution of Pheronema species from the N.E. Atlantic and the Mediterranean. 1736 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 81 records from Streuobstwiese Haus Zeitz. 341 records from Size of planktic foraminifera at CTD station PS55/019. 19 records from Coccolith counts of multinet SO119_MSN1301. 7089 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN739. 144 records from NABU-Auerochsenweide. 941 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 4326 records from Atlas der Raubfliegen Deutschlands - database. 122 records from Abundance of radiolaria at station UT99-20-1. 136 records from Assemblage of living benthic foraminifera in sediment core GeoB3715-1. 52 records from Catálogo digital y clave ilustrada de los mosquitos (Diptera: Culicidae) de las zonas áridas de los estados de Nuevo León y Tamaulipas, México. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 10915 records from Planktic foraminifera counts of sediment core MD95-2040. 96 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 471 records from Benthic foraminifera counts of sediment core GIK23342-6. 97 records from Düne am Ulvenberg (Darmstadt). 35260 records from imr_mareano_grab. 3240 records from Protected species bycatch in New Zealand fisheries. 10465 records from Stoneflies (Plecoptera) of Ireland. 48 records from Total foraminifera counts of multinet M21/5_MSN733. 92097 records from ALA species sightings and OzAtlas. 22 records from Coccolith counts of multinet M32/5_MSN979. 229 records from (Appendix 3, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core BMR96GC21 in the southeast Indian Ocean. 257 records from Observasjoner av plantearter ved kartlegging av Viktige naturtyper for naturmangfoldet i Frosta og Levanger i 2018. 133 records from Grillhütte Wettsaasen, Wiese, Hecken. 14549 records from Alterra (NL) - Comparison of entomofauna in four different habitats. 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 58888 records from Florida Keys Reef Visual Census 2009. 3203 records from Biodiversity assessment in the Yangambi Biosphere Reserve. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-087. 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 133 records from Abundance of radiolaria at station LV28-4-1. 1216 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé et du Plateau. Data mobilized in the framework of JRS Biodiversity Foundation project. 7074 records from Distribución y abundancia de aves marinas y acuáticas en regiones marinas prioritarias y áreas protegidas del Golfo de California y Golfo de México. 2273 records from Terrestrial mammals of Dobrogea Region, Romania. 144 records from Monitoreo biológico en la cuenca Jamundí - Subcuenca Pance Campaña ARA - RARE - CVC – Asociación Calidris. 402 records from Fossil occurrence of planktonic foraminifera from IODP Hole 315-C0001F. 25563 records from Plants of Ghana. 7942 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 51 records from Total foraminifera counts of multinet M21/4_MSN712. 3064 records from Epibenthos and demersal fish monitoring in function of aggregate extraction in the Belgian part of the North Sea. 1578 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 230 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 76 records from Total foraminifera counts of multinet M21/4_MSN724. 646 records from Abundance of nanoplankton in sediment core GeoB1028-5. 969 records from Caracterización biológica en la Serranía de San Lucas 2015. 165 records from Great Koala Count 2. 2394 records from EDP Baixo Sabor: Phytoplankton - Ecological Monitoring Program [2016]. 2 records from Benthic macrofauna abundance of sediment core 12930-022. 37 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 84 records from Total foraminifera counts of multinet M21/5_MSN728. 5778 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 146 records from BIRDRACE VdW Wilder Westen. 22 records from Liste des oiseaux de BZM Belambo. 650 records from Data collected on animal species through census using Kilometric Abundance Index (KAI) in Biosphere Reserve of W-Bénin. Data mobilized in the framework of JRS Biodiversity Foundation funded project in Benin. 147 records from Total foraminifera counts of multinet M21/3_MSN674. 41 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 11 records from Benthic macrofauna abundance of sediment core 13078-017. 47 records from Total foraminifera counts of multinet M21/4_MSN703. 4 records from Conocimiento de la diversidad y distribución actual del maíz nativo y Tripsacum en el estado de Tamaulipas. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 110 records from Birdrace-LiLaMai-Vechta. 1481 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 77 records from VFD-RP: Taunus: Ponykoppel Thurner. 5 records from Amphibians and Reptiles in Selected Sites in Palawan Province, the Philippines. 458179 records from Bird Atlas 2007 - 2011. 364 records from Monitoreo y seguimiento de fauna terrestre para el AID y AII de la Central Hidroeléctrica de Calima. 2017-B.. 91 records from BIRDRACE NABU LV Hessen. 61 records from Wälder im Hainbachtal. 157 records from BIRDRACE Rheinische Wasserrallen. 804 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 11 records from BenthosBarentsSeaPolarstern1991. 66 records from Langes Tannen(LMS), Klasse 5d. 5 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 114 records from Liether Kalkgrube. 173 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 10316296 records from OEH Atlas of NSW Wildlife. 33 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/011-3. 12 records from Bilder der Natur. 856 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 34 records from Total foraminifera counts of multinet M21/4_MSN715. 352 records from Tetraonid line transect surveys from Norway: Data from Statskog. 1096 records from Absolute abundance of particles and planktic foraminifera in sediment core GIK12310-4, Cape Barbas, North-West Africa (Appendix Tab. 2c). 1995 records from Barrow Island Ants. 1117 records from Biogeographic distribution of Antarctic and sub-Antarctic Cumacea. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 1767 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 50996 records from Karplanter i vernet barskog og edelløvskog. 97 records from Species composition in twelve (12) Afzelia africana Sm & Pers populations in Benin.. 59 records from Inventarios de fauna y flora en los DRMIs Embalse Peñol - Guatapé y Cuenca Alta del Río Guatapé, Las Camelias y el área a declarar Cuenca de San Pedro. 10 records from Kita-Wäldchen Fuchsturmweg Jena. 217 records from Data from ILAM surveys conducted by ARCOS in Bugesera landscape for year 2017. 882 records from (Appendix A4) Relative abundances of planktonic foraminifera of sediment core GeoB1706-2. 44 records from Wiesen am Treffpunkt Freizeit. 56 records from Lebensraum Walram. 63 records from Stadtbiotop Ulrichteich. 11 records from Avistamiento de Aves Corregimientos de Juanchaco y Ladrilleros, Buenaventura, Valle del Cauca - Septiembre 2016. 2795 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 30 records from Inventario nacional de especies vegetales y animales de uso artesanal. 81 records from Stadtpark Schmölln. 102 records from Waldwandel in Monschau-Mützenich-Boverei. 133 records from Manual para la identificación de lianas en el campo. 19 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Georgyi Ushakov" in 1992”. 13 records from Lauchhamer GEO-Tag der Artenvielfalt. 115 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 301 records from Dinoflagellate cysts of mooring MST-8 (station 905), full and empty cysts. 2157 records from Waarneming.nl (NL) - Great Grey Shrike Count 2007-2008. 306 records from (Table DR1) Biofacies, percentages of important benthic foraminifera and isotope data at ODP Site 758. 873 records from Diversidad y distribución altitudinal de maíces nativos en la región de los Loxicha, Sierra Madre del Sur Oaxaca. 106 records from Caracterización de la ornitofauna del Alto del Buey, Bahía Solano, Chocó. 317 records from Fuldaaue (Stadtgebiet Fulda). 160 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 4 records from Benthic macrofauna abundance of sediment core 13077-019. 1026 records from Distribution of major planktic foraminifer at Site 177-1088. 83 records from Naturpark Kottenforst-Ville 16.6.09. 401 records from All observations extracted from the Flora of Northumberland and Durham 1831. 269 records from BIRDRACE Dithmarscher Deichhühner. 270795 records from Florida Keys Reef Visual Census 2007. 226 records from Total foraminifera counts of multinet M21/1_MSN610. 122 records from BIRDRACE Grenzgänger. 781 records from Inventario de Aves y Mamíferos en humedales del departamento de Córdoba. 4 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335. 279 records from BIRDRACE Wannacks Topti(c)ker. 1 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Echinodermata. 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 2 records from Distribution of Quinqueloculina sp. in sediment core 13200-081. 164 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 51 records from Steinbachtal (Würzburg). 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 146 records from Wirbach. 58 records from Mamíferos laguna El Tinije. 94 records from Total foraminifera counts of multinet M12/3_MSN536. 106 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Thiankoye) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 78 records from BIRDRACE leucorhö statt logorrhö. 35 records from Planktic foraminifera of sediment core GeoB1404-3. 20 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 179 records from Área Otún Quimbaya - Densidad poblacional valores objeto de conservación Santuario de Fauna y Flora Otún Quimbaya, 2016. 112 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 5920 records from Alterra (NL) - Microarthropods inventories by Henk Siepel on various locations. 100 records from BIRDRACE Stuttgart 100 trööt. 48 records from Deutsche Schule Budapest. 123 records from Total foraminifera counts of multinet M11/1_MSN517. 138 records from Total foraminifera counts of multinet M12/3_MSN561. 5452 records from NPWS Seal Database. 16885 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 186828 records from Florida Keys Reef Visual Census 2003. 3 records from Trockenwiesen und angrenzender Waldrand im Hainbachtal. 376 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 307 records from (Table 2) Lithic grain and foraminifera shell counts in sediment core SU90-08. 254 records from Grünes Germersheim. 93 records from Total foraminifera counts of multinet M36/6_MSN1198. 79 records from Plasm bearing foraminifera counts of multinet M21/2_MSN628. 495 records from Plant (HBBG-PL). 118 records from Natur aus zweiter Hand am Muldestausee. 7 records from Recursos hidrobiológicos de Caño Cristales, La Macarena, Meta. 190 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 151 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/088-7. 136 records from Escarabajos estercoleros (Coleoptera: Scarabaeinae) asociados a dos fincas ganaderas de Rionegro, Antioquia (Colombia). 50 records from Ampliación de la base de datos de la ictiofauna insular del Golfo de California. 141 records from Kinderbauernhof Pinke-Panke. 23 records from TBW-Schafberg. 4611 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 95 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/045-2. 1144 records from 70 samples data of Kiel Bay. 76 records from Umgebung von Schorndorf. 1629 records from Biología poblacional de Isostichopus fuscus (Ludwig, 1875) (Echinodermata: Holothuroidea) en el sur del Golfo de California. 315 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 15 records from Bird Conservation Targeting Project (BCTP) in the UK, 2006-2011. 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 30 records from Leben auf einer Sturmfläche. 3 records from Nanai Cicada on the Namosi and Navosa Province, Fiji.. 26624 records from Monitoring data from the federal state Bavaria (Germany). 310 records from Stadtpark Herzberg (Elster). 130 records from Unser Schulhof - eine Apotheke. 338 records from Expedition "Schulgelände". 306 records from Lice (Phthiraptera) of Ireland. 5 records from Streuobstwiese (Mittelgasse 4). 1699 records from Base de datos de especies y especímenes de la flora costera del norte de Chile (plan RECOGE). 36 records from Berlin - Treptower Park / Karpfenteich. 201 records from Reconstruction of surface water temperature of sediment core GIK12310-4, Cape Barbas, North-West Africa (Appendix Tab. 3). 105517 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 297 records from Stausee (Oberdigisheim/Meßstetten). 87 records from Total foraminifera counts of multinet SO118_MSN1265. 184 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 3597 records from University of Amsterdam (NL) - Páramo Vegetation Research, Rabanal, Guerrero and Villa de Leyva paramo complex, Colombia. 7762 records from Proyecto COL88611 para la conservación y uso sostenible de ecosistemas secos. 22429 records from National fish tag database. 6 records from Antarctic Marine Species Sequence Data. 87 records from Gulf of Gdansk. 195204 records from Threatened species occurrences, Denmark 1991-2015. 149 records from Bayerische Donau - Neu Ulm. 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 6738 records from Regeneración de especies arbóreas del bosque mesófilo en las montañas del norte de Chiapas. 132 records from BIRDRACE Die Wetterauer. 527 records from Ascidiacea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 576 records from Ecological inventory of Borassus aethiopum (Mart.) populations in the Pendjari Biosphere Reserve, Benin. Data mobilized in the framework of JRS Benin project. 4 records from Abundance of microplankton from bottle APRIL-2000-K2. 1054 records from Mound building termites contribute to savanna vegetation heterogeneity- woody plants, forbs and graminoids. 4 records from DAYO: Invasive Alien Amphibians in the Philippines. 17 records from Nachtinsekten am Muldenufer. 40 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Ernst Krenkel" in 1992”. 68 records from Total foraminifera counts of multinet M21/4_MSN696. 895 records from Biodiversidad de moluscos opistobranquios (Mollusca: Opisthobranchiata), del Pacífico mexicano: Isla Cedros-Vizcaíno. 11 records from Oberservation of birds at station PS14/145 along 49° West. 17 records from Dinoflagellate cysts of sediment core IOW211660-6. 26 records from Nanoplankton abundance at station GeoB2021-3. 3 records from Records at sea of juveniles southern elephant seals (Mirounga leonina) from Península Valdés, Argentina. 4658 records from Macrobenthos monitoring at long-term monitoring stations in the Belgian part of the North Sea between 1979 and 1999. 28 records from Mastofauna presente en el Alto del Buey, Bahía Solano, Chocó. 545 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 80 records from Landschaftsschutzgebiet Schmutterwald. 67 records from Diversité des espèces menacées des zones classées et terroirs villageois du Bénin (Afrique de l'Ouest).. 538 records from Distribution of planktic foraminifera of sediment trap NB7. 352 records from Tag der Artenvielfalt. 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 1 records from DAYO: Invasive Alien Reptiles in the Philippines. 26 records from Chronicle of Nature - Phenology of Mammals of Kondinskie Lakes National Park named after L. F. Stashkevich. 544 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 784 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 3 records from Antarctic Jellyfish. 13 records from National Trust Species Records. 48 records from Australian National Wildlife Collection provider for OZCAM. 611 records from Aves asociadas a tres ventanas de la Orinoquia Colombiana - SULU I. 88 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 74 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 68 records from IBF Monitoring of Orthoptera. 13 records from Plantas de la cuenca alta y media del río Bita, Vichada (Colombia). 98 records from SuLaMa Microcebus griseorufus occurence data. 1 records from 5. Wiener Gemeindebezirk. 24 records from FND "Weißer Berg" Leißling. 214 records from NSG Haunestausee, Hauneteiche. 235032 records from River Murray Phytoplankton Monitoring. 12396 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Chiles-Cumbal, La Cocha-Patascoy y Doña Juana Chimayoy.. 83 records from VFD-H: Heidenrod: Weide am Ortsrand. 15 records from Meiofauna abundance in sediment core 12930-015. 11 records from Terre d'huiles. 99 records from Total foraminifera counts from M35/1_MSN1074. 185 records from Ostracoda in sediment core PS51/135-4. 91 records from BIRDRACE SchrägeVögel. 143 records from Planktic foraminifera counts at CTD station PS55/025. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 97 records from Streuobstwiese Stedar 2008. 101 records from Rund ums Schulgelände. 90 records from Südwestlich der Parkwiesen. 88 records from Monitoreo Pyrrhura calliptera, 2018. 133 records from Programa Integral de Protección de tortugas marinas. Temporadas 2007 a 2012. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 245 records from Innenstadt Göttingen - Natur Zuhause. 2158 records from Distribución potencial de las especies de la familia Psittacidae en México. 502 records from Aves de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 101 records from BIRDRACE nabu-rhein-main.de. 74 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 2097 records from Kartlegging av dragehode. 21886 records from Vascular plants in power line clearings and the nearby forest, southeast Norway. 1722 records from Occurrence records of southern African aquatic biodiversity. 4 records from Microplankton abundance at bottle station SEPT-1999-K3. 23 records from Phytoplankton abundance in surface water in 1993, Ancon, Peru. 1 records from Fauna carcinológica de México. Crustáceos estomatópodos y decápodos del Golfo de México. Río Bravo, Tamaulipas a Cabo Catoche, Q.Roo. 43 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1017. 13 records from Greg Dawe Sightings. 105 records from Sealife Tracker. 28 records from Uferzone Wipper (Biesenrode). 154 records from Bammentaler Duft- und Heilkräutergarten. 402 records from Tag der Artenvielfalt in Heidelberg. 96 records from Birdrace-federleser-Herford. 8 records from Chronicle of Nature - Phenology of Arachnids of Kondinskie Lakes National Park named after L. F. Stashkevich. 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 323 records from Inventaire floristique dans le cadre le cadre de l'Aménagement de la forêt classé de l'Amou-Mono (Togo). 111 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 103126 records from ANTAVIA TrackingKing. 344 records from Caracterización de fauna para el establecimiento de nuevas Reservas Naturales de la Sociedad Civil en Arauca. 36280 records from EDP Foz Tua: Bat Roosts - Ecologial & Compensatory Measures Monitoring Programs [2011-2017]. 415 records from Dinoflagellate cysts from sediment core PS2138-1. 101 records from Steinbruch Kronungen. 11 records from Oberservation of birds at station PS14/142 along 49° West. 79 records from Lahnufer in Villmar. 1970 records from peqrb_c_populationandcommunitydynamics_2001-2011. 195 records from FNL e.V.. 159 records from Planktic foraminifera assemblage in sediment core SU90-I06. 103 records from Conocimiento integral del tapir (Tapirus bairdii) y el pecari de labios blancos (Tayassu pecari) en México. 105 records from Schulgarten Hans-Carossa-Oberschule. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 26 records from Corvids Literature Database. 184 records from Klasse 3a. 3552 records from Liste des récoltes par Herbier de dépôt TOGO. 24 records from Kaisertal. 24 records from Coccolith counts of multinet M32/5_MSN990. 75 records from Naturpark Kottenforst-Ville 19.6.09. 42 records from Status and spatial diversity of Sorghum wild species in Malawi.. 26 records from Angelberger Forst - Klassen 3 a und 3 b. 13 records from Tag der Artenvielfalt am Bruckenwasen. 92 records from Birdrace-Team_BO-bachter-Bochum. 5281 records from (Table 1) Distribution of benthic foraminifera on sediment core PS2837. 17 records from Meiofauna abundance in sediment core 13200-024. 328 records from renaturierter Main (Kemmern bei Bamberg). 276 records from Contribución a la distribución, ecología y estado de conservación de dos especies del género Sceloporus, endémicas de la región del Cabo, Baja California Sur. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 60 records from Total foraminifera counts of multinet FCA97C_MSN1344. 93 records from Anfibios de un sector del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO- 2017. 282 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2009. 109 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 4 records from Zwischen Enz und Schule. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 51 records from Chronicle of Nature - Phenology of Insects of Kondinskie Lakes National Park named after L. F. Stashkevich. 112 records from Abundance of planktic foraminifera at CTD station PS55/037. 4 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 39 records from Total foraminifera counts of multinet M21/4_MSN710. 4919 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 229 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto48-56. 305 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 1 records from Anfibios y reptiles del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 152 records from Investigación y manejo para la conservación de tortugas amenazadas de los humedales llaneros. 15 records from Chronicle of Nature - Phenology of Amphibia of Kondinskie Lakes National Park named after L. F. Stashkevich. 31 records from Regenwasserabfangbecken. 3 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 388 records from Mooswald (Freiburg). 131 records from Abundance of planktic foraminifera at CTD station PS55/083-1. 2072 records from Inventaire et dénombrement des oiseaux du Parc Naturel Communautaire de la Vallée du Sitatunga au Sud Bénin. 55 records from Flora und Fauna am Mittelrheintal. 70 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Horèwendou) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 33 records from Schüler erforschen die Helme-Aue. 115 records from Lebensraum Stadt und Park. 21220418 records from Norwegian Species Observation Service. 2 records from Tejidos de Anfibios y Aves, en estudios bióticos en el Complejo de Páramos Chingaza. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 217307 records from Manscape. 114 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 10 records from Benthic macrofauna abundance of sediment core 13077-023. 12 records from Oberservation of birds at station PS14/158 along 49° West. 11 records from Waldgebiet Todtnau- Sonnhalde. 9139 records from Composition and distribution of the biomass of zooplankton in the central Arctic Basin 1975, 1976, 1977. 448 records from Ants on Nukunonu atoll in 2011. 42 records from sbosch. 15123 records from Modern foraminifera in the New Zealand EEZ. 142 records from Total foraminifera counts of multinet M21/3_MSN661. 15 records from Benthic macrofauna abundance of sediment core 13200-047. 193 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 64 records from Schafheide im Böblinger Wald. 73 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1196. 76 records from Caracterización Floristica del Páramo Tatamá. 429 records from Toxicity of copper, cadmium and zinc to Macquarie Island marine invertebrates 2012/15. 75 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 27 records from Bäche im Mooswald (Vörstetten). 77 records from GEO-Tag am Hohlen Stein. 168 records from Monitoreo biológico en la cuenca RUT, campaña ARA - RARE - CVC – Asociación Calidris. 2 records from Dinámica poblacional de Mammillaria crucigera y Neobuxbaumia macrocephala en la región de Tehuacán-Cuicatlán. 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 852 records from Data on medicinal plants of Benin. 235250 records from ABV - Common breeding birds in Flanders, Belgium. 26 records from Macroinvertebrados de la ciénaga La Honda, Tanguí. 11 records from Benthic macrofauna abundance of sediment core 13077-059. 342 records from Aquatic animals of the Kamogawa River Basin (Fukuoka, Japan) with the photo images. 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 28 records from Insekten. 121 records from Southern Giant Petrel census data within the Australian Antarctic Territory. 4924 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 2570 records from Reef Life Survey - Survey Records. 17 records from Schutzgebiet Ochtersum. 638 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 6 records from Ecología, genética y conservación de la caoba (Swietenia macrophylla): herramientas para un manejo adaptativo de la selva Maya de Quintana Roo, México. 117 records from Plasm bearing foraminifera counts of multinet M21/1_MSN619. 278 records from BIRDRACE Usedommeln. 24 records from Inventory of plant species produced in CERF nuseries. 60 records from Reifrocknarzissenwiese Löcknitz. 151 records from Abundance of radiolaria at station UT99-22-1. 1325 records from Análisis de integridad biológica en el Parque Natural Regional (PNR) El Vínculo. 15 records from Tiere. 10 records from Feuchtwiesen Wippertal bei Wippra. 1116766 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 339 records from Database of Eurasian beaver (Castor fiber L., 1758) in Natural Reserves and National Parks of Russia. 337591 records from Dry Tortugas Reef Visual Census 2012. 2 records from Distribution of Quinqueloculina sp. in sediment core 13200-039. 6 records from Poliquetos invasores (Annelida: Polychaeta) del Puerto de Mazatlán, Sinaloa. 42 records from Stadtwald Heide. 303 records from Elasmobranquios del sistema laguna Chantuto-Panzacola y Carretas-Pereyra de la Reserva de la Biósfera La Encrucijada, Chiapas. 203 records from Benthic macrofauna abundance of subcores of sediment core 12930-065. 4 records from Naturschwimmteich Casa Bianca. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 95 records from BIRDRACE BiBi. 144 records from Lustbach-Umland. 389 records from Distribution of planktic foraminifera of sediment trap NB6. 42596 records from Ireland's BioBlitz. 30 records from Höhle am Neuweg / Sächsische Schweiz. 155 records from Concentration of siliceous microplankton in surface sediments, brine. 23 records from Benthic macrofauna abundance of sediment core 13200-075. 336 records from Eschlberg Thalhausen. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-015. 82 records from Crinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 1656 records from Siliceous microfossil occurrence, Site 177-1094. 2175 records from Invasión de Pinus spp y la conservación de la diversidad florística en Los Altos de Chiapas, México. 188 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_91MC. 114 records from Birdrace-Finkenspötter-München. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 110 records from BIRDRACE Angeliter Ornis. 72 records from Total foraminifera counts of multinet M36/2_MSN1107. 205 records from Echuya Bird Species Survey 2018. 1104 records from Mid Ulster Hare Surveys 2012-2015. 65 records from Schulhof A.-Lindgren-Schule (Elmshorn). 147 records from Trockenhang Greinhartsberg Edelfingen. 23 records from Caracterización biológica de la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia. 221 records from Mangfalltal. 24941 records from African Plants - a photo guide. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 209 records from Dicotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 838 records from Vanuatu dugong sightings recorded during CMS dugong catch / by-catch standardised questionnaire 2015-2017. 44 records from Plasm bearing foraminifera counts of multinet M21/5_MSN735. 163 records from Tiere und Pflanzen am Pfannenbach. 965 records from Norwegian freshwater lake fish inventory. 791 records from Análisis de Integridad Biológica para el Distrito de Conservación de Suelos Cañón del Río Grande. Convenio CVC- Univalle 108 de 2017. 180 records from Ecología poblacional de Abies hickelii en el Pico de Orizaba, Veracruz. 384 records from Distribución y aspectos taxonómicos de los corales pétreos (Anthozoa: Scleractinia) del Pacífico mexicano. 208 records from Außengelände KITA "Mäuseburg" Waldkirchen. 87 records from Klütwald. 24 records from Ornithologische Wanderung um Tussenhausen. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 529 records from NINA insect database. 33 records from Planktic foraminifera of sediment core GeoB1402-5. 3971 records from Avifauna de la Isla de Cozumel, Quintana Roo. 734 records from Fauna y flora del municipio de Paipa, Boyacá. 263 records from Macromycetes in Portugal Update. 4 records from House Sparrow Parks Project, London, 2009-2010. 2870 records from Vegetation assessment and forest dynamic study of various areas in Gabon from 2000 to 2018. 1985 records from Seabird 2000. 46 records from Total foraminifera counts of multinet FCA97C_MSN1340. 2 records from Atlaszeder in Oma´s Garten. 89 records from Flora de las Barrancas del Cobre. 41 records from Total foraminifera counts of multinet M21/4_MSN711. 226 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/011-3. 300 records from Landschaftsschutzgebiet "Holmer Sandberge". 92 records from Höltigbaum. 389 records from Wildes Bremer Leben im Park. 1986 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 90 records from BIRDRACE TicTacToe. 1013 records from Icota - Pelagant. 455 records from nazza. 3149 records from Shark Bay Survey. 213 records from Microzooplankton abundance measured on water bottle samples at station PS58/043-2. 59 records from Schriesheimer Steinbruch. 36 records from Plöwener Wald. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/038-3. 366 records from Tracking Australia - arid wildlife track-based monitoring. 99 records from BIRDRACE TEAM BO-BACHTER. 55 records from Zitadelle Berlin-Spandau (7b). 170 records from EDP Foz Tua: Fish – Complementary Studies [2011]. 6 records from Boimstorfer Sundern. 129 records from Distribución geográfica de las lagartijas partenogenéticas del género Aspidoscelis en México. 4364 records from General Biodiversity Records from Ireland. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-059. 446 records from Territorial Andes Occidentales - Densidad poblacional ensamblaje de aves, 2017. 19695 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 215 records from Microzooplankton abundance measured on water bottle samples at station PS58/046-3. 68 records from Sandhofen. 52 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 208 records from Inventory of Synsepalum dulcificum Daniell in south Benin. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 100 records from DNA metabarcoding assays reveal a diverse prey assemblage for Mobula rays in the Bohol Sea, Philippines. 14 records from Benthic macrofauna abundance of sediment core 13200-020. 175 records from Neißetal. 106 records from Dinoflagellate cysts from sediment core PS2458-4. 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 172 records from City of Kalamunda Biodiversity Inventory. 132 records from Sukzession Industriebrache. 529 records from Creación de la base de datos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, y de la reserva de la biosfera Islas del Golfo de California para el grupo de los mamíferos. 4 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 94 records from Distribution of calcareous foraminifers in sediment core Well 6406/8-1. 864 records from Status, ecología y conservación de loros Amazona en el Noreste de México. 7569 records from Darling Scarp Survey. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 169 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 65 records from Avifauna de la reserva de la biosfera El Cielo, Tamaulipas, México. 62 records from Plasm bearing foraminifera counts of multinet SO118_MSN1251. 150 records from Sonnentaugemeinschaft. 30 records from Riekdahler Wiesen. 2 records from Algas coralinas articuladas (Rhodophyta-corallinales) de México. 57 records from Schulgelände Städtisches Gymnasium. 193 records from Sapo National Park Chimpanzee Survey 2016. 103 records from Anfibios y reptiles de la sierra de Cuatro Venados, Oaxaca, México. 1176 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 2 records from Modelación de la distribución geográfica de las especies del género Abies presentes en México. 18 records from Meiofauna abundance in sediment core 12930-018. 6 records from Occurrence of mammalia relicts at site Barova Cave. 2042 records from Elasmobranquios del Golfo de Tehuantepec, litoral chiapaneco. 10 records from schlittschuhweiher. 4 records from Microplankton abundance at bottle station SEPT-1999-K9. 68 records from Total foraminifera counts from M35/1_MSN1059. 530 records from SPC PROCFish/C Invertebrates Observations Tuvalu 2004-2005. 265 records from FFH-Gebiet Ahrbachtal. 85 records from Naturerlebnisraum Koppelsberg (Plön). 2168 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo Páramos Chilí - Barragán, Tolima. 170 records from Total foraminifera counts of multinet M10/2_MSN231. 1053 records from Distribution of major planktic foraminifera at Site 177-1089. 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 30004 records from Conservation Atlas Surveys. 22 records from Ictiofauna Presente en la Ciénaga de Montaño, Municipio del Carmen de Atrato. 13 records from Benthic macrofauna abundance of sediment core 12930-059. 35 records from NNI Riverbase - Mosses & Liverworts. 5704 records from MEL AVH data. 191 records from Caracterización biológica de la ventana de biodiversidad enclave Atuncela, municipio de Dagua, Valle del Cauca. 744 records from Área Galeras - Estructura Anturio 2016 - 2017. 11 records from Analyses of the recent components in the sand fraction of sediment core PS1422-1. 220 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 30 records from Weed Population Genetics. 1404 records from Fish data of the Belgian River Meuse from 1989 to 2012. 88 records from Birdrace-WeserEggeLäufer-Höxter. 1647 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 194 records from Bodenteicher Seewiesen. 23 records from Caracterización de la ictiofauna de la ciénaga Honda, Tanguí. 201 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 1852 records from Flora marina (Clorophyta, Phaeophyta, Rodophyta) y fauna conspicua (Echinodermata, Mollusca, Polychaeta) del Complejo Insular Espíritu Santo-Cerralvo-San José en BCS, México. 26 records from Schulteich Heinrich-Mann-Schule. 9557 records from BioChem: Davis Strait and Baffin Bay Zooplankton. 170 records from Biotop "Kohlbeke" (Berlin-Marzahn). 25883 records from Monitoring data from the federal state Saxony (Germany). 105 records from BIRDRACE Kiesmätze. 336 records from Kremmer Luch. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 11 records from Benthic macrofauna abundance of sediment core 12930-028. 13 records from Benthic macrofauna abundance of sediment core 12930-039. 25176 records from Bees of Ireland. 19 records from Coccolith counts of multinet M32/5_MSN988. 18 records from Meiofauna abundance in sediment core 13077-060. 4318 records from Registro de Fauna Silvestre en el Inventario Nacional Forestal y de Fauna Silvestre-SERFOR, Perú. 2953 records from Avifauna de la laguna Madre de Tamaulipas. 22876 records from imr_mareano_beamtrawl. 348 records from Stadtgebiet (Dannenberg). 89 records from Total foraminifera counts of multinet M10/2_MSN298. 94 records from Plasm bearing foraminifera counts of multinet M12/3_MSN557. 20 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5115-1. 126 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 61 records from Biosphärenreservat Münsinger Alb. 3 records from Phyto and Zoo benthose of Chabahar Bay, Gulf of Oman 2012-2013. 1111 records from Inventario de algas, corales pétreos, moluscos, crustáceos decápodos, equinodermos y peces de las islas de Revillagigedo, Colima, México. 2 records from Observadores del Mar - Crustáceos Decápodos. 13 records from Meiofauna abundance in sediment core 13200-012. 45 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 93 records from Algas perifíticas del cerro Tacarcuna en el marco del proyecto Colombia BIO-2017. 244 records from Marine flora and fauna records from the North-east Atlantic. 101 records from Actualización de la taxonomía y distribución de los anfibios y reptiles de San Luis Potosí. 109 records from Birdrace-Team_Charadrius-Günzburg. 82 records from Total foraminifera counts from M35/1_MSN1049. 89 records from Schulgelände Paul-Gerhardt-Schule. 366 records from Inventaires des adventices dans les bas-fonds rizicoles de Sérédou (CESP16-0022-Guinea). 112 records from Plasm bearing foraminifera counts of multinet M21/2_MSN640. 136 records from Plasm bearing foraminifera counts of multinet M21/1_MSN609. 51013 records from ClimateWatch. 3 records from Inventario ficoflorístico de las comunidades arrecifales del Parque Nacional Bahías de Huatulco, Oaxaca. 111 records from Rund um das LUGY. 67 records from Total foraminifera counts from M35/1_MSN1056. 155 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 102 records from Vertebrados terrestres de San Juan de Camarones, Durango. 1092 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 765 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 458279672 records from EOD - eBird Observation Dataset. 36 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/049-3. 88 records from Plasm bearing foraminifera counts from M35/1_MSN1053. 125 records from Conservación de serpientes de cascabel de la península e islas del Golfo de California y del Pacífico. 115 records from Avistamientos de Biodiversidad Marina / Marine Biodiversity Sightings. 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 171 records from Total foraminifera counts of multinet M21/6_MSN787. 47 records from Schulgelände Ceciliengymnasium. 141 records from Censo nacional del jaguar y sus presas (1a etapa). 18 records from Spielwiese. 1 records from Waldtag in und um Seelingstädt. 356 records from Biotope in Rheine - Aktion 350. 24 records from Steinbruch Mainz-Weisenau, 4.Jahr. 42 records from Feuchtwiese Grüne Mitte, Klasse 5a. 1005 records from MVZ Bird Observations (Arctos). 13 records from Tiere im Teichgebiet. 6 records from Occurrence of mammalia relicts at site Henauhof NW 2. 495 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 303 records from Abejas silvestres (Hymenoptera: Apoidea) de la región Praderas de Tokio-El Potosí - Sierra Mazmorras - Cañón de Iturbide, Coahuila y Nuevo León, México. 138 records from Total foraminifera counts of multinet M21/3_MSN676. 1096 records from Diagnóstico y Propuesta de Manejo de la Flora Arbórea y Arbustiva Urbana del Municipio de Viterbo - Caldas. 138 records from Planktic foraminifera counts at CTD station PS55/030. 141 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 67 records from Liberia National Pygmy Hippo Action Plan Data. 106820 records from Florida Keys Reef Visual Census 2004. 190 records from Gelände des Schulzentrums am Himmelsbarg. 113 records from (Table 3) Occurrence of benthic foraminifera in the Ledyanaya section. 54 records from Königsdorfer Wald. 8339 records from Siliceous microfossil occurrence, Site 177-1093. 22 records from Mastofauna Presente en la Ciénaga de Montaño, Municipio del Carmen del Darién, Chocó. 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 7 records from Die Bachspezies. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 14547 records from PlantTracker data from 2012 onwards. 40 records from Seagrass Monitoring at Chengue Bay, Colombia. 29 records from Stonefly (Plecoptera) records from Britain and Ireland, via iRecord. 9265 records from APIS - Antarctic Pack Ice Seals 1994-1999, plus historical data from the 1980s. 10297 records from Xeno-canto - Bird sounds from around the world. 27 records from Caracterización de Reptiles del corredor biológico Cértegui - Yerrecuí - Amurrupá. Sector Amurrupá. 66 records from Under-ice Amphipods in the Greenland Sea and Fram Strait (Arctic): Environmental Controls and Seasonal Patterns Below the Pack Ice. 23720 records from Database of the Distributions of Marine Fishes of Arctic Canada. 85 records from Rund um den Hainbergsee. 64 records from Pilzlehrwald. 76 records from Birdrace-Birding_for_Nature-Bonn. 3403 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 234 records from Danisco-Wiese. 601 records from LBV 100 - Artenvielfalt am Rothsee. 1600 records from EDP Foz Tua: Bat Roosts - Baseline and Complementary Studies [2008-2010]. 117 records from Abundance of radiolaria at station UT99-5-1. 42 records from Mammal ocurrences in vineyards of Andalusia (Spain). 26 records from Plasm bearing foraminifera counts from M35/1_MSN1052. 44 records from Flora und Fauna in unserer Kita. 52445 records from Biodiversity Now / Nature Check (Biodiversitet Nu / NaturTjek). 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 145 records from Total foraminifera counts of multinet M10/2_MSN332. 113 records from Flora. 538 records from 20 Jahre Naturschutzgebiet Dreienberg. 260 records from Copepoda of the Equatorial Eastern Pacific. 84 records from BIRDRACE Avinauten. 3255 records from Aves laguna El Tinije. 7876 records from Inventario de la fauna arrecifal asociada al ecosistema de Pocillopora en el Pacífico Tropical Mexicano. 110 records from EDP Foz-Tua: Cabrera vole (Microtus cabrerae) & Small Mammals - Baseline Studies [2008]. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 54 records from Total foraminifera counts of multinet M21/4_MSN707. 114 records from Especies de peces registradas en el canal principal y afluentes de los ríos Lengupá y Upía en Boyacá. 565 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2008. 121 records from Stever. 51 records from Naturnachmittag 'Artenvielfalt an der Ecke' (Wäldchen an der Wegegabelung). 180 records from Total foraminifera counts of multinet M21/2_MSN656. 5 records from Schulwald Regionale Schule Sprendlingen. 1095 records from DIBA-Parc de la Serralada Litoral. 1 records from Hausgarten. 246 records from Berkel. 123 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/041-5. 12070 records from Bird survey of Budai salt pans in Taiwan. 51 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1009. 195 records from Avifauna Asociadas al Cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 930 records from Diversidad de grupos selectos de vertebrados (Reptilia, Amphibia) e insectos (Lepidoptera: Papilionoidea y Hesperioidea; Odonata; Diptera: Bombyliidae) en el Valle de Cuatrociénegas y Sierra de la Madera, Coahuila, México. 23606 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores tuna fishery from 1998 on: during navigation or search mode. 25 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5133-1. 10 records from Ökowerk Emden. 53 records from Total foraminifera counts of multinet M21/4_MSN713. 62 records from Total foraminifera counts of multinet M21/4_MSN700. 70 records from Parkuntersuchung Weißer See. 1090 records from Southern Ocean Ostracoda (except Halocypridina). 1 records from University of North Carolina at Chapel Hill Herbarium. 95 records from Abundance of radiolaria at station UT99-19-2. 23 records from Distribución, abundancia, estructura poblacional y potencial reproductor de Zamia furfuracea L.. 499 records from Planktic foraminifera of sediment core GeoB1710-3. 85 records from Total foraminifera counts from M35/1_MSN1043. 30 records from DENOMBREMENT SIMULTANE ET SYNCRONISE DES OISEAUX D’EAU MIGRATEURS AU TOGO. 373 records from Foraminifera abundance of sediment core AC85-4. 158 records from Mamíferos colectados en expedición al Río Apaporis - Proyecto Colombia BIO. 55909 records from DIBA-Parc Natural del Montseny. 249 records from Coleoptera of Genting Highland, Malaysia: Species richness and diversity changes along the elevations. 85519 records from Irish Butterfly Monitoring Scheme. 2832 records from Situación actual del búho manchado mexicano (Strix occidentalis lucida) y de los Strigiformes de la Reserva de la Biósfera La Michilía. 246 records from Spredning av fremmede arter med tømmerimport til Norge. 18 records from Schulhof (Bad Waldsee). 46 records from Hainbachtal in Oelsnitz/V.. 2934 records from Caracterización biológica del Monumento Natural Yaxchilán como un elemento fundamental para el diseño de su plan rector de manejo. 59 records from Oschenberg, NO von Bayreuth-Laineck. 5 records from New Zealand fish and squid distributions from research bottom trawls 1964-2008. 27 records from Wiese hinter der Schule (Darmstadt). 67 records from Recopilación de Información de FLORA en la Jurisdicción de CORNARE, hasta el año 2015. 3425 records from Macrobenthos monitoring in function of dredge disposal monitoring in the Belgian part of the North Sea. 1440 records from Fish Species Occurrence Records for Uganda Mobilized from Observation Archives. 167 records from Schlattstaller Tal (Lenningen). 35 records from Antarctic Isopods. 6644 records from Mayflies (Ephemeroptera) of Ireland. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 2 records from Inventory of Antarctic seabird breeding sites. 9521085 records from naturgucker. 17 records from Benthic macrofauna abundance of sediment core 13200-077. 4 records from Microplankton abundance at bottle station SEPT-1999-K2. 202 records from Anfibios y reptiles de la cuenca alta y media del río Bita, Vichada (Colombia). 64 records from Análisis ecológico de la ornitofauna de la ciénaga La Honda, Tanguí. 303 records from Zooplankton from selected sites in Ghana. 14 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 63-125 µm fraction. 2 records from Parthenaue. 76 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 2200 records from Zoobenthos data from the Southern Beaufort Sea, 1971-1975. 65 records from BIRDRACE Federal Birds of Investigation FBI. 47 records from Total foraminifera counts of multinet M10/2_MSN284. 18365 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 1 records from Anfibios y reptiles en el municipio Medina, Cundinamarca - Proyecto Colombia BIO. 98 records from Total foraminifera counts of multinet M21/2_MSN644. 1344145 records from Chinese Wild Bird Federation Bird Records Database. 214 records from Murciélagos observados en la transición Andino Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 31 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1331. 272 records from Interacciones en el dosel de la selva húmeda tropical e implementación de un sistema de estudio en este ambiente. 1570 records from Modelaje de la Distribución geográfica de Pinus pseudostrobus y P. leiophylla. 85 records from Birdrace-Die_Paradiesvögel-Herford. 21 records from Breitkopfbecken (Berlin-Reinickendorf). 87 records from Landschaftsschutzgebiet Buchhorst 4. 1 records from Peces de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 26487 records from EDP Foz Tua: Bat Habitats - Ecologial & Compensatory Measures Monitoring Programs [2011-2017]. 135 records from Total foraminifera counts of multinet M21/1_MSN614. 1 records from Biological observations from the Discovery Investigations 1925-1952. 152 records from Estuarine fish in the Rewa River estuary, Viti Levu, Fiji 2012. 127 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 188 records from Bekkerøye (Salvelinus fontinalis) i Norge 2013. 132 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 101 records from Revisión periódica de Agave victoriae-reginae en el apéndice II de la CITES. 100 records from Birdrace-The_Ringers-Friesland. 115 records from Planktic foraminifera assemblage in sediment core GIK16396-1. 6 records from 2. Donauinsel bei Entau. 4007 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 100 records from Plasm bearing foraminifera counts of multinet SO117_MSN1244. 50 records from Planktic foraminifera counts of sediment core A180-73. 405 records from Planktic foraminifera assemblage in sediment core GIK17050-1. 124 records from Total foraminifera counts of multinet M21/2_MSN641. 620 records from Censo nacional del jaguar y sus presas (1a etapa). 1541 records from (App 11) Relative contents of mass species of planktonic foraminifera in sediments from Core S-17954. 46 records from Liether Park (LMS), 5a. 701 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 216 records from Naturpark Drömling. 446 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 25 records from Inventory of plant species in plantations in Benin. 3276 records from Inventario de corales pétreos, asteroideos, equinoideos y peces óseos de arrecifes de la costa de Jalisco, Colima y Michoacán. 19598 records from WCPS Bird Survey Project. 79 records from Balkon (Norderstedt). 106 records from Sylter Meerstrandläufer. 37 records from Avistamiento de Aves en la Reserva de la Sociedad Civil "El Diamante de las Aguas" Marzo 2017. 53 records from Mamíferos medianos y grandes en la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 3006 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 165 records from Plasm bearing foraminifera counts of multinet M21/1_MSN608. 2109 records from Harvestmen (Opiliones) of Ireland. 13 records from Benthic macrofauna abundance of sediment core 12930-063. 145 records from Überall ist Wunderland. 12 records from Mystaya. 18 records from Filogeografía y genética del paisaje de Cactoblastis cactorum en la región del Caribe. 490 records from Riedensee. 6 records from Bayerische Donau - Metten. 2680 records from New Zealand research tagging database. 105 records from Landschaftsschutzgebiet Buchhorst 3. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 45 records from Pfrimmersbachtal. 360 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 78 records from Rössewiesen am Krumbholz. 26 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 1997 records from Aves de la cuenca media del río Bogotá. 2650 records from Obtención de la riqueza de aves y selección de especies susceptibles de monitoreo en la zona noroeste en el estado de Chiapas. 351 records from Insectos de los Parques Ecológicos Distritales Humedales de Bogotá, D.C.. 198 records from Total foraminifera counts of multinet M10/2_MSN218. 101 records from Flora de macroalgas del litoral oaxaqueño. 172 records from Total foraminifera counts of multinet M21/6_MSN789. 51 records from Kindervilla Außengelände. 102 records from BIRDRACE Niederrheinische Bartgeier. 124 records from Total foraminifera counts of multinet M21/1_MSN615. 103 records from Marine biological observation data from coastal and offshore surveys around New Zealand. 138 records from Monitoreo biológico en la cuenca Sonso, campaña Agua ARA - RARE - CVC – Asociación Calidris. 132 records from Wulfsmuehle/Pinnau. 2236 records from Áreas de crianza de tiburones en el Golfo de California. 11 records from Meiofauna abundance in sediment core 13368-015. 134 records from VFD-H: Rheingau: Pferdeweide Loock. 1770 records from Southern Ocean octopus. 284 records from schulgarten. 142970 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 21 records from Tauchen und Meer 02. 1469 records from Stable oxygen isotope ratios of foraminifera from late middle Eocene sediments of ODP Site 171-1052 from Blake Plateau, West Atlantic Ocean (Appendix). 318 records from Benthic foraminifera groups of ODP Site 162-982. 808 records from Lake Muir Wetlands. 151 records from Macroinvertebrate groups found on deep-sea volcanic habitats in the Galapagos Marine Reserve in the Eastern Tropical Pacific Ocean: Echinoderms. 184 records from Área Galeras - Estructura vegetal Encino (Weinmannia mariquitae), 2016. 116 records from Área Tatama - Densidad poblacional Bangsia Tatama, 2018. 84 records from Anisopodidae and Thaumaleidae (Diptera: Nematocera) of Ireland. 19012 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 186 records from NSG Berschau - Auengebiet (Neustadt / Wied). 2661 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé t du Plateau. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 198 records from Monitoreo biológicos en la cuenca Frayle, ARA - RARE - CVC – Asociación Calidris. 136 records from Oberes Schindelbachtal. 42 records from Kleinstbiotop mit Schulteich/Weißwasser. 210 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 14 records from Benthic macrofauna abundance of sediment core 13077-098. 1129 records from Monitoreo de la abundancia de juveniles de langosta Panulirus argus como índice de reclutamiento inminente en Sian Ka'an (Reserva de la Biósfera). 57 records from Seagrass_data_Solomon Islands_2018. 1900706 records from SAFRING: Historical Bird Ringing Records (2005-2009). 47574 records from Fungimap. 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1056. 4 records from Collections and observation data National Museum of Natural History Luxembourg. 1070 records from Análisis de Integridad Biológica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 40 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 24443 records from National Mammal Atlas Project, online recording. 428 records from Benthic foraminifera counts of sediment core GIK23351-1. 13 records from Benthic macrofauna abundance of sediment core 13077-063. 844 records from Birds (UWEP-BI). 91 records from Birdrace-Die_TUErteltauben-Tübingen. 218 records from MATRIX project, monkeys near Kampala in Uganda. 4163 records from National Lesser Horseshoe Bat Database. 2419 records from Esponjas, corales escleractinios, equinodermos y peces de arrecifes coralinos del norte y sur de Veracruz. 106 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 67 records from Total foraminifera counts of multinet M21/5_MSN740. 273 records from Assemblage of living benthic foraminifera in sediment core GeoB3713-1. 186 records from Schulhof Goethe-Gymnasium (Emmendingen). 15 records from Urwald 2 (Bad Waldsee). 1643 records from SPC PROCFish/C Invertebrates Observations Papua New Guinea 2006. 145 records from BIRDRACE Dith Marsh Sandpiper. 259 records from A nest-site survey of Barn swallow at railroad stations in the Kinki District,south-central Japan. 300 records from Marine Data from The Wildlife Trusts (TWT) Dive Team; 2014-2017. 1178 records from Status, distribución, ecología y conservación de las cotorras serranas (Rhynchopsitta pachyrhyncha y R. terrisi) en el norte de México. 4400 records from Distribution of planktic foraminifera of sediment core M35027-1. 243 records from Aves de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 94 records from FFH-Gebiet Paartal. 72 records from Schulumfeld Albert-Einstein-Gymnasium (Sankt Augustin). 124 records from Schulprojekt (Bremen). 44 records from Georgs-Padd (Wangerooge). 1 records from Registro de Ateles belzebuth (mono araña) en el municipio de Yopal, departamento de Casanare. 183 records from Microzooplankton abundance measured on water bottle samples at station PS58/041-2. 1352 records from SPC PROCFish/C Invertebrates Observations French Polynesia 2003, 2004 and 2006. 13 records from RISC and ALERT Marine Non-Native Species (Chinese Mitten Crab, Wakame and Carpet Sea Squirt) Records. 5 records from Feuchtwiese. 348 records from Datos de ocurrencia de triatominos americanos del Laboratorio de Triatominos del CEPAVE (CONICET-UNLP). 1179 records from Avifauna de ocho localidades del corredor de conservación Paraguas – Munchique de Colombia.. 207 records from Species Composition and Abundance of Zooplankton in the Nearshore Beaufort Sea in Winter-Spring 1978-1980. 69 records from Área Las Hermosas - Cantidad de area ocupada Danta, 2018. 114 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 66 records from Total foraminifera counts from M35/1_MSN1064. 30 records from Geführte Wanderung im Eselsbachtal. 362 records from Censo nacional del jaguar y sus presas (1a etapa). 2695 records from Point Count Data for TIDE's Private Land (Block 127), Belize 2009-2013. 86 records from Inventario Español de Especies Terrestres (MAGRAMA). 126 records from Schulwald Marksuhl. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 25 records from Nanoplankton abundance at station GeoB2017-4. 18 records from Planktic foraminifera assemblage in sediment core GIK17724-1. 97 records from Grenzturm Hohen Neuendorf. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 1983 records from Vertebrados silvestres en zonas indígenas de la reserva de la biósfera Mariposa Monarca: anfibios y reptiles. 108 records from Rasgos funcionales de la vegetación en el cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO. 99 records from Plasm bearing foraminifera counts of multinet M12/3_MSN558. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 548 records from OPAL New Zealand Flatworm Survey - flatworm sightings. 15 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 302 records from Kohlstattbrunnental. 50 records from Riqueza específica y biodiversidad de microartrópodos edáficos de la Isla de Cozumel, Q. Roo. 102 records from Muehlenbach bei Friesheim. 677 records from Census of secondary forest of Itchèdè-Toffo (Southern Benin). 788 records from ABC_Nyika National Park-Uledi_sampling event data. 73 records from Total foraminifera counts of multinet POS231/3_MSN1330. 146 records from Luch Niederlehme, Schüler der Klasse 7. 179 records from Ictiofauna de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 2 records from uno city. 232 records from Werremündung im Schwarzatal. 146 records from Assemblage of living benthic foraminifera in sediment core GeoB3702-2. 331 records from Langes Tannen (Uetersen). 100 records from Feriendorf Ober-Seemen. 112 records from BIRDRACE Gütersloher Gimpel. 709 records from Bergkamen- Bergehalde Großes Holz. 1229 records from Moth Records of Ireland. 8 records from Aktion des Romain-Rolland-Gymnasiums. 13 records from Benthic macrofauna abundance of sediment core 13200-052. 52 records from Anfibios presentes en las lagunas del municipio del Medio Baudó. 17 records from Caracterización Ecológica de la Mastofauna del Cerro Tacarcuna, Unguía, Chocó. 57 records from Occurrence of mammalia relicts at site Moladova V. 191 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 79 records from Total foraminifera counts of multinet M12/3_MSN541. 17 records from Benthic macrofauna abundance of sediment core 12930-065. 79 records from GymnQuerfurt. 365 records from Benthic foraminifera counts of sediment core GIK17730-4. 10855 records from WDC Shorewatch Sightings. 10 records from Oberservation of birds at station PS14/157 along 49° West. 146 records from Verified Marine records from Indicia-based surveys. 169 records from Planktic foraminifera counts at CTD station PS55/051. 117 records from Plasm bearing foraminifera counts from M35/1_MSN1062. 931 records from Determinación del estado de las poblaciones silvestres del cocodrilo de pantano (Crocodylus moreletii) en México y evaluación de su estatus en la CITES. 2269 records from Temporal and spatial variation of waterbirds at Sayula Lagoon, Jalisco, Mexico: a five-year winter season study. 360 records from Wälder bei Nordkirchen. 996 records from Especies ornamentales invasoras: el caso de Kalanchoe delagoensis. 45 records from Promachocrinus kerguelensis. 1169 records from Makira. 1872 records from Esponjas, corales escleractinios, equinodermos y peces de arrecifes coralinos del norte y sur de Veracruz. 216 records from Assemblage of living benthic foraminifera in sediment core GeoB3711-1. 50 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1338. 1255 records from Waarneming.nl (NL) - Great Grey Shrike Count 2010-2011. 71 records from Caracterización de coberturas vegetales en el páramo de Rabanal. 15 records from Die geheimnisvolle Welt der Spinnen. 1321 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 857 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 356 records from BioBlitz Barcelona 2010-14. 56 records from SuLaMa Amblyomma chabaudi occurence data. 15973 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 236 records from Bird Banding Data for Cockscomb Basin Wildlife Sanctuary, Belize 2017-2018. 1110 records from FFH-Gebiet "Calwer Heckengäu". 163 records from Herpetofauna de la reserva de la biósfera Valle de Tehuacán-Cuicatlán (etapa final). 19 records from Meiofauna abundance in sediment core 13368-003. 1794 records from Elephant Seal Sightings, Heard Island. 424 records from Australian Native Plants Society, Canberra Region. 171 records from Sahrbachtal Kreis Ahrweiler. 57 records from Lüner Holz (Lüneburg). 82 records from BIRDRACE Buteo2DO. 1042 records from Línea base biótica del proyecto de Restauración Ecológica Re-Viva La Primavera. 22 records from Potencial económico de la flora útil de los cafetales de la Sierra Norte de Puebla. 28 records from Caracterización de la fauna del páramo del Duende, litoral del San Juan, Chocó. 405 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 242 records from Schulbiotop Dr.-Gustav-Schickedanz-Hauptschule (Fürth). 40 records from Coccolith counts of multinet M32/5_MSN971. 564 records from Distribution of calcareous nannofossils in the lower sequence of the CIROS-1 sediment core (Table 2). 2782 records from Point Count Data for Payne's Creek National Park, Belize 2008-2013. 62 records from Total foraminifera counts of multinet M10/2_MSN229. 100 records from Schwanseepark (87645 Schwangau). 501 records from Relative abundance of planktonic foraminifera in sediment core MK-316. 59 records from Presencia de la tortuga tapaculo (Kinosternon dunni) en dos localidades del departamento del Chocó. 712 records from Aprovechamiento sustentable y conservación de la palma bola (Zamia furfuracea), especie endémica protegida, en la zona de Los Tuxtlas, Veracruz. 114 records from BIRDRACE VIE will rock you!. 503 records from Inventario fitopatológico de las especies vegetales dominantes en la región de Zapotitlán de las Salinas, Pue.. 766 records from Reptiles and Amphibians Distribution Atlas 1978 (An Foras Forbartha). 4096 records from Zooplankton abundance in the Kerguelen Axis region 2016. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 83 records from BIRDRACE Die Frankenpfeifer. 2977 records from Grasshoppers, Crickets and Allied Insects (Orthoptera) of Ireland. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 3125 records from Alterra (NL) - Entomofauna inventory in edges of arable fields province of Groningen. 6958 records from Siliceous microfossil occurrence, Site 177-1091. 295 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto11-19. 2 records from Diversidad de orquídeas en la región El Momón-Margaritas-Montebello, Chiapas, México. 105 records from Tag der Artenvielfalt in der Stadt Luzern. 117 records from Streuobstwiese Stedar 2009. 149 records from Total foraminifera counts of multinet M21/2_MSN640. 120 records from Assemblage of living benthic foraminifera in sediment core GeoB3703-4. 24 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/108-1. 179 records from L’évaluation environnementale du projet de barrage de la retenue d'eau, à Sangaredi (Boké), pour la Société minière Guinea Almuna corporation (CESP2016-022). 1 records from Estudio ecológico-florístico de los enclaves de vegetación xerofítica inmersos en una selva baja caducifolia en el Istmo de Tehuantepec, Oaxaca. 17 records from Meiofauna abundance in sediment core 13077-058. 94 records from Vielfalt verschiedener Wiesen. 63 records from Rund um die Sausenburg. 1791 records from Plant (NSMK-PL). 518 records from Área Galeras - Monitoreo Restauración, 2016. 446 records from Bayerische Donau - Blindheim Donaubrücke. 50 records from Mühlenbach bei Buxtehude. 283 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 518 records from (Fig. 3) Absolute abundance of dead benthic foraminifera in sediment core PS1394-3. 6 records from Grünanlagen Stadt Brandenburg an der Havel. 411 records from DIBA-Provincia de Barcelona y Red de Parques Naturales. 163 records from Entomofauna laguna El Tinije. 137 records from Total foraminifera counts of multinet POS231/3_MSN1334. 177 records from BIRDRACE Die Kielbris. 32 records from Caracterización Floristica del Paramo de Frontino o del Sol. 4872 records from Abundance and diversity of the Amphipoda (Crustacea) from the Greenlandic shelf. 62 records from Erft in Selikum (Neuss). 166 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 51577 records from POPA- Fisheries Observer Program of the Azores: Seabird sightings in the Azores tuna fishery from 2000 on: during navigation or search mode. 269 records from BIRDRACE speedbirder. 2954 records from Establecimiento de línea base para el monitoreo de especies de plantas de interés para la conservación. 48 records from Plasm bearing foraminifera counts of multinet SO118_MSN1266. 1252 records from Distribución, abundancia y riqueza específica de la avifauna terrestre en la Isla Espíritu Santo, Baja California Sur, México. 15 records from Wasserbachsee. 275 records from Aves de tres Macro Hábitats en la región de la Mojana, Sucre, Colombia. 49 records from Schrebergarten Düsseldorf Oberkassel. 37 records from Plasm bearing foraminifera counts of multinet M27/2_MSN879. 3311 records from Australia's Census of Antarctic Marine Life project - IYGPT Data collected on the CEAMARC cruise 2007/08. 33 records from Planktic foraminifera assemblage in sediment core GIK23074-3. 43 records from Planktic foraminifera counts of sediment core A180-72. 24 records from Analyses of the recent components of sediment core PS1402-2. 210460 records from Limnodata. 46528 records from Atlas of Danish Fishes. 1 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Echinodermata. 29 records from Caracterización Ecológica de la Mastofauna del Alto Galápagos. 682 records from Megabenthos-Epibenthos Greenland. 78 records from Plasm bearing foraminifera counts from M35/1_MSN1051. 2373 records from Waarneming.nl (NL) - Great Grey Shrike Count 2008-2009. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 5629 records from Temporal evolution of zooplankton by Regent net in the Northwestern Mediterranean Sea,Villefranche-sur-mer, 1959-2010.. 2138 records from Eppingen und Umgebung. 36525 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 196 records from Halberg bei Neumorschen. 18 records from Herpetofauna del Alto Galápagos, San José del Palmar, Chocó. 468 records from Mamíferos voladores laguna El Tinije. 90 records from Birkenloh. 423 records from Species observations during citizen science expeditions. 1500 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Day/night stratified zooplankton sampling onboard the Norwegian R/V Jan Mayen. Program ALV. 254 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 24 records from Liether Park (LMS), 6b. 6655 records from Composición florística y estructura de dos parcelas permanentes en bosques secos tropicales del municipio de Méndez, Tolima. 457 records from NSG Karwendel. 616 records from Chronicle of Nature - Phenology of Plants of Bryansk Forest Nature Reserve (plot based). 80 records from Total foraminifera counts of multinet M12/3_MSN562. 2270 records from SPC PROCFish/C Invertebrates Observations Fiji 2002-2003. 777 records from Early succession in benthic hard bottom communities in Kongsfjorden, Svalbard - abundance. 619 records from Asteroids from French subantarctic islands: records from the Marion Dufresne MD03 expeditions. 4 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 38 records from Coccolith counts of multinet SO119_MSN1278. 63 records from Issumer Fleuth. 1547 records from Alterra (NL) - Entomofauna inventory in Speulder forest. 28 records from Sandgrube Zaisertshofen. 243 records from (Table 2) Absolute abundance, diversity, and relative abundance of benthic Foraminifera species in Upper Pleistocene - Holocene bottom sediments from Core Vulk-34-90. 245 records from Small rodents trapped in old growth forest in Vegårshei, Norway. 60 records from Mamíferos de dos procesos para la conservación de relictos de bosque seco de la cuenca media – baja del Río Meléndez para la declaratoria de un Área Protegida Pública y para la Consolidación del SIMAP y fondo del agua de Cali. 123 records from Artenbestimmung. 632 records from Lustadter Wald .. 36 records from Variación de la diversidad y la bioacumulación de Mercurio del ensamblaje de anfibios en un gradiente altitudinal con actividad minera, en el PNN Farallones de Cali. 130878 records from IMOS - AATAMS Facility Satellite Relay Tagging Program - Delayed mode data. 156 records from Botanischer Garten (Saarbrücken). 14 records from SuLaMa blind cave fish occurence data. 104 records from Caracterización Florística de un Área Degradada por Actividad Minera en la Costa Caucana. 28 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 16 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 1 records from AquaInvaders. 101 records from Total foraminifera counts of multinet POS231/3_MSN1335. 1 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 110 records from Implementación del programa de monitoreo del cocodrilo del pantano (Crocodylus moreletti) México-Belice-Guatemala: región de coordinación MXRC2-Golfo Centro, Veracruz centro y norte Oaxaca [Temporada 2013]. 11 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5117-1. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 203 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 29 records from Klimaoasen in Köln. 23 records from Wiese Niederaula. 22 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1337. 79 records from BIRDRACE Blinde Hühner. 21 records from Caracterizacion de mamíferos del Cerro de Chageradó (Frontino- Antioquia), 2011. 10 records from Riqueza de especies y biodiversidad edáfica de una zona de humedales del Parque Nacional Arrecife de Puerto Morelos, Quintana Roo, México. 797 records from Diversidad biológica y conservación del ecosistema de los perros llaneros (Cynomys ludovicianus) en México. 1 records from Concentración Lixiviados. 12 records from Benthic macrofauna abundance of sediment core 12930-081. 170 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 14794 records from Phytoplankton Species Composition, Abundance and Cell Size in San Francisco Bay: Microscopic Analyses of USGS Samples Collected 1992-2014. 111 records from Landesweite NABU-Vogelrallye. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-039. 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-09. 137 records from Assemblage of living benthic foraminifera in sediment core GeoB3705-2. 8 records from Mamíferos de un Área Degradada por Actividad Minera en la Costa Caucana. 84 records from Estudio poblacional y conservación del mono araña (Ateles geoffroyi yucatanensis) en la región nororiental Península de Yucatán. 270 records from Planktic foraminifera assemblage in sediment core SU90-I03. 540 records from (Figure 2a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3209. 121 records from Owere Fiddel. 15 records from Beisetal bei Niederbeisheim. 316 records from Total foraminifera counts from multinet M32/5_MSN974. 37 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 480 records from Incorporación a la base de datos de CONABIO del material de la Colección Halffter (Coleoptera: Scarabaeinae). 2885 records from (Appendix B) Abundance of benthic foraminifera in sediment cores GIK17964-3 and GIK17964-2. 19 records from Auenwiesen und Trockenrasen. 139 records from Distribución del Manatí (Trichechus manatus) en la cuenca baja del río Sinú en el departamento de Córdoba. 27 records from Planktic foraminifera assemblage in sediment core GIK23041-1. 138 records from Plasm bearing foraminifera counts of multinet M21/2_MSN652. 168559 records from Vulnerable marine ecosystems in the South Pacific Ocean region. 216 records from Registros biológicos del Humedal Santa María del Lago 1999-2013. 1 records from Environment Agency Rare and Protected Species Records. 82 records from BIRDRACE Die Ziegeneier. 380 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_88MC. 139 records from BIRDRACE Turbine Untersee. 10 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 203 records from Total foraminifera counts from multinet SO119_MSN1281. 30 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5130-2. 55 records from Caracterización de la Ornitofauna del Alto Galápagos, San José del Palmar, Chocó. 4 records from Distribution of Quinqueloculina sp. in sediment core 13078-013. 5 records from Wanninchen. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 103 records from Mammifères: Etude d'état initial de la biodiversité dans la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 42517 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 74 records from Schulwald Grundschule Brügge. 699 records from Diatom assamblage in samples from sediment trap OG3. 5 records from Ceriantharia distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 14722 records from BANDAPHO, BAse de DAtos sobre Aphodiidae. 28 records from Planktic foraminifera assemblage in sediment core GIK23055-2. 182 records from Total foraminifera counts of multinet M21/2_MSN652. 119 records from Nanoplankton abundance at station GeoB2021-1. 332797 records from National Wetland Inventory (NV). 240323 records from Fishbase. 491 records from (Table 1) Relative abundances of planktic foraminifers in bottom sediments from Core AMK4-316GC. 1500 records from Ground Census Data for Lake Nakuru and Nairobi National Parks. 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 53549 records from Online Atlas of Vascular Plants 2012-2020. 66 records from Área Las Hermosas - Cantidad area ocupada oso, 2018. 23 records from Planktic foraminifera assemblage in sediment core GIK23256-1. 674 records from (Table S1) Key calcareous nannofossils and the range chart of the genera Gomphiolithus, Diantholitha and Fasciculithus of ODP Site 208-1262. 69 records from BIRDRACE Mathilden-Käuze. 6 records from Abundance of two benthic foraminifera species in sediment core 12930-007. 8876 records from El Censo Neotropical de Aves Acuáticas en Colombia (CNAA): 2002 - 2011. 45 records from Caracterización Ecológica de la avifauna del Cerro Jánano. 126 records from BIRDRACE Duckehühnchen. 50 records from Biodiversidad en el valle de Cuatro Ciénegas.. 101 records from Urwald 1 (Bad Waldsee). 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 17 records from National Plant Monitoring Scheme - Northern Ireland. 118 records from ABC_Mafinga Forest Reserve Vegetation survey. 122 records from Birdrace-Hügelland-Mainz/Bingen. 122 records from Wiesenbiotop am Wasserturm. 1321 records from Regeneración, crecimiento y dinámica poblacional del pino azul Pinus maximartinezii Rzedowski. 104 records from BIRDRACE Andechser Stativträger. 578 records from (Figure 2c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3239. 1 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 1347 records from Colección de mamíferos de la Universidad del Valle. 3679 records from IBF Monitoring of Lichens. 195 records from Total foraminifera counts of multinet M21/6_MSN766. 9 records from Willersalpe. 137 records from NSG Leist bei Ziegenhain. 8775 records from SuLaMa bird occurence data. 30 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 342 records from Inventario herpetofaunístico de la reserva de la biosfera La Sepultura, Chiapas, México. 56 records from Heidesee / Halle. 178 records from Caracterizacion de la avifauna del Cerro de Chageradó (Frontino- Antioquia), 2011. 27 records from Phytoplankton abundance in surface water in 1992, Ancon, Peru. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 113 records from Total foraminifera counts of multinet M21/2_MSN642. 107 records from El rorcual común Balaenoptera physalus, en el Golfo de California, México. 72 records from Küste Wismar-Wendorf bis Hoben. 15 records from Kühnauer Aue und Kühnauer See. 482 records from Kühmark bei Wetzlar. 1137 records from SPC CoFish Invertebrates Observations Federated States of Micronesia 2006. 55690 records from The First Atlas of Wintering Birds in Britain and Ireland: 1981/82-1983/84.. 125 records from Regionalpark(Hattersheim). 113 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 62 records from Hettstadt Gehäge. 770 records from A crowdsourcing approach to collecting photo-based insect and plant observation records. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN658. 201 records from Área Galeras - Cantidad de área ocupada Venado 2015-2017. 61 records from Fürstenberger Ralley Teil 3. 132 records from Aachtobel. 49 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 597 records from Fish species occurrence and composition in selected Ugandan water bodies, 2001-2003. 304 records from Schlichemquelle (Tieringen/Meßstetten). 366 records from Palynomorpha in sediment core IK9373-10 from the Laptev Sea. 112 records from Total foraminifera counts from M35/1_MSN1070. 151 records from Total foraminifera counts of multinet M12/3_MSN533. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 61 records from GE-Brühl. 1316 records from Recurso hidrobiológico de los manglares de la Zona de Uso Sostenible de la Balsa (ZUSLB) y la Zona de Recuperación de Tinajones (ZRT). 136 records from Planktic foraminifera counts at CTD station PS55/018. 153 records from Bergbaufolgelandschaft am Muldestausee. 18 records from Mittelstreifen. 400 records from Shieldbug & allied species records, from iRecord. 102 records from Mamíferos asociados a cuatro ventanas de la Orinoquia Colombiana - SULU I. 4963 records from Canberra Nature Map. 8406 records from Alas del Arroz. 1647 records from Diatom assamblage in samples from sediment trap NB6. 13 records from Benthic macrofauna abundance of sediment core 13200-081. 52 records from Total foraminifera counts of multinet M10/2_MSN268. 30 records from Phytoplankton abundance in surface water in 1995, Ancon, Peru. 306 records from Size of planktic foraminifera at CTD station PS55/037. 1 records from Haslauer Moor. 8864 records from Aves de los Parques Ecológicos Distritales Humedales Bogotá, D.C.. 106 records from Total foraminifera counts of multinet M11/1_MSN524. 241 records from BIRDRACE RennVögel Münsterland. 47 records from Spandau HBO. 134 records from Planktic foraminifera counts at CTD station PS55/082-1. 53 records from Park Schönfeld (Kassel). 20 records from Abundance of benthos infauna at station GIK23037-3. 2434 records from (Table T1) Abundance of planktic forminifera in ODP Site 177-1090. 21818 records from VIMS Chesapeake Bay Multispecies Monitoring and Assessment Program. 265 records from Size of planktic foraminifera at CTD station PS55/084-1. 6 records from Fitoplancton marino frente a Baja California. 2. Áreas de surgencias de la región Ensenadense. 30 records from Aves de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 30-63 µm fraction. 14 records from Abundance of epibenthic echinoderms at seafloor photography station M21/4_250. 153 records from VFD-BW, Schwäbische Alb: Pferdeweiden Zainingen. 274 records from Ecología e historia natural de Schistocerca americana socorro y S. piceifrons piceifrons en Isla Socorro. 1108 records from Waarneming.nl (NL) - Great Grey Shrike Count 2013-2014. 14 records from Analyses of the recent components of sediment core PS1400-4. 241 records from Kiesgruben Wemb. 1333 records from Análisis de la distribución y estructura de las poblaciones de Echinocactus platyacanthus Link et Otto, en el Valle de Zapotitlán, Puebla. 4 records from Schulbiotop und Brigach (Villingen). 241 records from Greenland Macrobenthos Young Sound, 1996. 2610 records from Fire in Gimlet Woodlands. 176 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto75-83. 187 records from Ökostation (Freiburg). 998 records from Plant (MNHM-PL). 112 records from Planktic foraminifera counts at CTD station PS55/037. 843 records from Koala Count. 50 records from Total foraminifera counts of multinet M10/2_MSN251. 2370 records from Aves y mamíferos del Parque Nacional Sierra de Órganos, Zacatecas. 19 records from Flora y vegetación de la región terrestre prioritaria Tacaná-Boquerón, Chiapas, México. 2 records from Metallesthes specimens inspected and supporting information published in Metallesthes revision. 11 records from Anfibios y reptiles del estado de Nuevo León. 147 records from Assemblage of living benthic foraminifera in sediment core GeoB1720-3. 83 records from Spechtwald. 104 records from Feriendorf des Kreises Gedern (Ober-Seemen). 6 records from Reptiles and Amphibians Dataset. 79 records from Total foraminifera counts of multinet M12/3_MSN543. 14872 records from University of Melbourne Herbarium. 228 records from Föhrenried (Fronreute und Baindt). 168 records from Total foraminifera counts of multinet M21/3_MSN687. 40 records from Altholzparzelle Eilenriede Hannover. 171 records from Distribution and diversity of sipunculan fauna in high Arctic fjords (west Svalbard). 813 records from HARPOST - Hoppekreps og muslingkreps. 25 records from Cerdos asilvestrados (Sus scrofa) en la Reserva de la Biosfera Sierra La Laguna: Evaluación e impacto sobre la biodiversidad. 22 records from Inventarios de flora y fauna en bosques de niebla del municipio de Chámeza, Casanare. 95 records from LauWi. 255 records from Mitochondrial lineages in the Antarctic sea slug Doris kerguelenensis. 11 records from Chronicle of Nature - Phenology of Fishes of Kondinskie Lakes National Park named after L. F. Stashkevich. 2574 records from Sapo National Park Bio-monitoring Data. 106 records from BIRDRACE Die Schwenker-Birder. 429 records from Área Galeras - Estructuras Frailejón (Espeletia pycnophylla), 2016. 129 records from BIRDRACE Birding Bentheim. 1731 records from peqrb_b_populationandcommunitydynamics_2000-2011. 57 records from Total foraminifera counts of multinet M21/4_MSN718. 187 records from Radiolaria assemblage in sediment core GIK17722. 351 records from Flora (vascular) y fauna (aves) de los Parques Nacionales del estado de Baja California: Constitución de 1857 y Sierra San Pedro Mártir. 8489 records from Insect Collection of the Laboratory of Applied Entomology of the Faculty of Sciences of the University of Lome. 870 records from Monitoring of non-crop plants in organic fields of Mauritius. 90 records from Plasm bearing foraminifera counts of multinet M21/2_MSN648. 156 records from Relative abundance of planktonic foraminifera in sediment core L-348. 44 records from Leegmoor (Moormerland/Leer). 35 records from Gym Freyung. 228 records from Avon Baselining - Invertebrates. 340 records from Caracterización de las coberturas vegetales en el gradiente altitudinal Páramo-Bosque en los complejos de Páramo de Guerrero y Altiplano Cundi-boyacense. 419 records from Dinoflagellates of sediment core GeoB1523-1. 133 records from Abundance of radiolaria at station LV28-43-2. 66 records from Klostergarten St Luzen. 11 records from BID-AF2015-0004-NAC Collection de Diptères du LEA-UL. 300 records from Flora Mycologica Iberica Project database. 848 records from Santander Bio: Cepario del Laboratorio de Microbiología y Mutagénesis Ambiental de la UIS (LMMA). 756 records from Florística de las cactáceas de Durango. 11090 records from ZooplanktonNOGAP32b1986. 18 records from Meiofauna abundance in sediment core 54301-014. 126 records from Industriegebiet (Kempen). 163 records from Total foraminifera counts from multinet M31/3_MSN914. 242 records from Biología del murciélago mastín enano (Eumops bonariensis nanus) en Yucatán. 27 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5121-1. 49637 records from Monitoring data from the federal state Hesse (Germany). 57 records from Total foraminifera counts from M35/1_MSN1057. 72910 records from NINA Vanndata øvrige arter. 20 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5132-3. 39 records from Physical properties, geochemistry and ostracoda abundance of sediment core Lz1080. 180 records from Schussenaue (Weingarten). 4 records from Abundance of microplankton from bottle APRIL-2000-K4. 14 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 23 records from Alter Nördlicher Friedhof (München). 99 records from Rur. 21 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 229647 records from Waterbird census in Spain. 9 records from Wiesendreieck Luckenwalde. 20 records from Diversity and distribution of sorghum wild species in Malawi. 3947 records from The importance of host tree age, size and growth rate as determinants of epiphytic lichen diversity in boreal spruce forest.. 378 records from Size of planktic foraminifera at CTD station PS55/077-1. 121 records from Inventario de crotálidos en las zonas áridas del noroeste de México. 7 records from Kaulsdorf. 407 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 8279 records from The atlas of breeding birds in Małopolska. 21 records from Dellwiger Bach (Dortmund). 151 records from Biosphärenreservat Mittelelbe. 235 records from Total foraminifera counts from multinet M31/3_MSN905. 39 records from Soolbach-Tal. 134 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto66-74. 853 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 521 records from Bayerische Donau - Leipheim. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-051. 395 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_100MC. 664 records from Naturschutzgebiet Sistig-Krekeler-Heide. 1662 records from Questagame weekly feed. 138 records from Total foraminifera counts of multinet M10/2_MSN297. 228 records from Naturschutzgebiet Bausenberg (Niederzissen). 643 records from Polychaetes from two subtidal rocky shores of the North coast of Crete, collected for the NaGISA project 2007-2008. 370 records from Fossil occurrence of planktonic foraminifera from IODP Hole 315-C0001H. 108 records from BIRDRACE Die TUErteltauben. 52 records from Aktion der Klasse H2 in Simmelsberg. 2060 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 7 records from Plant Species Recorded at Elluokrom in Ghana. 550 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 38 records from USGS NRP - Submerged Aquatic Plants - 1966-2009. 642 records from Observation records of Amphibians. 104 records from Lilaeopsis brisbanica Population Study. 334 records from Kiesbagger (Mittelhausen). 292 records from Implementación del programa de monitoreo del cocodrilo del pantano (Crocodylus moreletti) México-Belice-Guatemala: región de coordinación MXRC2-Golfo Centro, Veracruz centro y norte Oaxaca. 459992 records from Royal Dutch Angling Association (SVN) - Piscaria. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 29481 records from SEAPOP - Last observation per locality in winter season. 18 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 91 records from Relative abundance of live benthic foraminifera of sediment core M5/2_88MC. 89455 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 154 records from Planktic foraminifera assemblage in sediment core GIK13289-1. 49 records from Artensuche auf den Elbwiesen in Radebeul. 138 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-070. 127 records from BIRDRACE Southernmost Lakers. 23 records from Tümpel Schulbiologiezentrum. 491 records from Naturschutzgebiet Lüneburger Heide. 20 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 94 records from ABC Ndangopuma Hills Sampling event data10_11_2005. 220 records from Microzooplankton abundance measured on water bottle samples at station PS58/045-2. 48 records from Wahner Heide LK 12 Biologie. 318 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction >150 µm. 632 records from Pollen analysis of sediment core GIK16856-2. 134 records from Abundance of planktic foraminifera at CTD station PS55/079-1. 64 records from Feuchtbiotop Weidenkaule. 18 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 21 records from Fishes of Ghana. 222 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 117 records from Fishes in MZNA-VERT: baseline freshwater sampling campaigns. 173 records from VFD-BW, Dinkelberg: Pferdeweiden Oberminseln. 53985 records from Marine sites, habitats and species data collected during the BioMar survey of Ireland.. 42 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 12 records from Ficha de Sonora aemula. 108 records from Censo aéreo de poblaciones de borrego cimarrón (Ovis canadensis cremnobates) en Baja California, México. 603 records from Polish Arctic Marine Programme. 97 records from Cirripedia distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bo
Keywords: GBIF; biodiversity; species occurrences